Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Controls on morphology of catchment-fan systems in the northwest margin of the Junggar Basin, northwest China - Zixiao Peng; Jianhua Qu; Zhijie Zhang; En Xie; Hongying Zhou; Li Wan; Dawei Cheng; Shunli Li; Xinghe Yu (Journal of Asian Earth Sciences, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Multi-omics integration and machine learning define an iron-sulfur cluster/zinc-binding protein prognostic signature in esophageal squamous cell carcinoma - Wenhuan Chen; Tongtong Chen; Zhixuan Li; Wan Lin; Zefeng Xie; Hansheng Wu; Liyan Xu; Enmin Li; Hefeng Zhang; Yinwei Cheng (Mammalian Genome, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Double macrocyclic cationic crosslinked network enabling ultrafast and efficient aqueous Cr(Ⅵ) remediation - Xinyi Deng; Haonan Cheng; Xinyu Yang; Jinhong Ye; Haibo Wan; Daoyong Chen (Water Research, 2026)

From fixed to condition-dependent emission factors: probabilistic tabular learning for wastewater N2O inventories - Jia-ji Chen; Hong-Cheng Wang; Wan-Xin Yin; Yu-Qi Wang; Jia-qiang Lv; Wen Wang; Ai-Jie Wang (Water Research, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Machine learning-driven prediction and control system for practical application of sulfur-based autotrophic denitrification biofilters - Jia-Qiang Lv; Jia-Min Xu; Wen-Ke He; Hong-Cheng Wang; Chong-Gang Liang; Ze-Run Cheng; Wan-Xin Yin; Yun-Peng Song; Jia-Ji Chen; Yanchen Liu; Bing-Jie Ni; Hao-Yi Cheng (Water Research, 2026)

Functional characterization of a plant germacrene D-4-ol synthase enabling the production of bioactive α-cadinol and τ-muurolol under changed catalysis conditions - Shao-Jun Cheng; Shi-Jie Liu; Wan-Jun Liang; Qin-Qin Shen; Zhong-Zhu Yuan; Zong-Hua Xiao; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Transversal variation of intramuscular fat and morphological characteristics of bovine longissimus thoracis et lumborum muscle - Junyoung Park; Chang Wan Sun; Sumin Song; Huilin Cheng; Choeun Im; Teak Soon Shin; Hyun-Jun Kim; Gap-Don Kim (Meat Science, 2026)

Continually evolving time-constant networks enable proactive control of coagulation for low-cost drinking water treatment - Yin Lu; Wan-Xin Yin; Yu-Qi Wang; Yun-Peng Song; Jia-Ji Chen; Jia-Min Xu; Fang Huang; Ding-Ding Tang; Meng Wu; Yan Zhou; Xiong Qin; Yong-Ji Wang; et al. (Journal of Water Process Engineering, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Pt-K synergy facilitates NOx storage and conversion for enhanced soot oxidation on 3DOM LaAlO3 perovskite - Quanshui Jing; Detao Xia; Xi Zhang; Huanlong Cheng; Gongde Wu; Yongliang Lu; Nengjie Feng; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2026)

Rational design of an S-Scheme CoTe@COFs-LZU1 heterojunction: Enabling rapid separation of photogenerated carriers and enhancing photocatalytic performance - Yuzhuo Wan; Yuqi Wan; Sen Zhao; ZhenFeng Zhong; Qingrong Cheng (Journal of Environmental Chemical Engineering, 2026)

Portable plasmonic nanoparticle sensor for rapid and visual monitoring of food freshness - Shang-Yi Yi; Peng-Hua Cheng; Ching-Wen Hwang; Jia-Wei Jheng; Tzung-Hai Yen; Dehui Wan (Food Chemistry, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Quaternary ammonium compounds in paired indoor dust and human urine: suspect screening and exposure associations - Fangyi Li; Zhendong Yang; Tingyu Li; Jiayong Lao; Kenneth M.Y. Leung; Xueyu Cheng; Zhengzhe Wan; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Mitigating side reactions in lithium metal batteries via initiator-modulated in-situ polymerization of a poly(1, 3-dioxolane) gel electrolyte - Yongquan Zhang; Sen Wang; Jingshun Wang; Cheng Wan; Jingrun Hu; Xianqiu Wu; Changhai Zhang; Tiandong Zhang; Yue Zhang; Qingguo Chi (Chemical Engineering Journal, 2026)

CMOS-compatible Eu2+-doped CsCu2I3 films with improved quantum yield for white-light emission and information encryption - Daoping Peng; Lichun Zhang; Xiaoxuan Li; Xiao Zhang; Yu Fang; Chenxi Han; Ziyan Wan; Xiaohua Cheng; Guanying Xie; Zhongqiang Wang; Congcong Liu; Mengmeng Jiao; et al. (Chemical Engineering Journal, 2026)

Insights into EPS-mediated simultaneous dewatering and stabilization of landfilled tannery sludge via combined chemical conditioning and PVD-vacuum preloading - Yang Xu; Fei Jin; Xiaowen Liu; Weixin Cheng; Ran Yu; Jia-Lei Wan; Jia-Hao Xie; Yan-Jun Du (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Field-deployable RspCas13d platform for rapid and extraction-free detection of giant panda- and canine-derived Canine Distemper virus - Qian Tao; Yuxiao Xing; Haidi Yang; Linhua Deng; Ming He; Yanxi Cheng; Qian Wang; Zhan Gao; Haohong Wan; Desheng Li; Shanshan Ling (Analytica Chimica Acta, 2026)

Semi-Analytical Solution to 3D Tunneling Face Stability Considering Excess Pore Pressure - Yang Cheng; Zi-Xuan Cui; Ze-Hang Qian; Zhen-Yu Yin; Wan-Huan Zhou (Transportation Geotechnics, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Non-neuronal acetylcholine-induced nitric oxide signaling promotes fluid transport in Malpighian tubules of Mythimna separata - Dong Cheng; Lei Yi; Xinjie Deng; Baijun Sheng; Qing Dong; Yutong Wan; Weining Cheng; Shumin Lü (Insect Biochemistry and Molecular Biology, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

Sedimentary records of silicate weathering on the continental shelf of the South Yellow Sea during glacial periods - Jin Zhang; Shiming Wan; Yifei Yang; Shouye Yang; Peter D. Clift; Yulong Guo; Debo Zhao; Yi Tang; Zhaojie Yu; Zehua Song; Zhongjing Cheng; Zaibao Yang; et al. (Science China Earth Sciences, 2026)

Proof-of-Concept Beam-Position-Resolved Backscatter Measurements of Three Preserved Cultured-Fish Specimens Using Calibrated High-Frequency Narrow-Beam Broadband Acoustics - Shujie Wan; Jing Cheng; Zhijun Wang; Guodong Li (Fishes, 2026)
High-frequency broadband acoustics can provide fine spatial resolution for near-range fish measurements, but the performance and limitations of beam-position-resolved backscatter measurements require careful evaluation. This proof-of-concept study examined one commercially sourced, dead, previously frozen specimen of each of three cultured fishes: golden pompano (Trachinotus ovatus; 24.4 cm), mandarin fish (Siniperca chuatsi; 29.1 cm), and large yellow croaker (Larimichthys crocea; 31.2 cm). A 650–750 kHz narrow-beam system was referenced to a 10.3 mm tungsten-carbide sphere, and matched-filter pulse compression and 1° stepwise scanning were used to estimate a beam-position-resolved backscatter metric along each body. At broadside incidence, the section-summed backscatter indices were −33.61, −22.45, and −33.07 dB for the T. ovatus, S. chuatsi, and L. crocea specimens, respectively. The section-summed abdominal backscatter index, in the region occupied by the swimbladder in the post-thaw X-ray images, exceeded the arithmetic mean of the head and tail group indices by 9.71 ± 1.84 dB (range: 8.27–11.86 dB). Tailward beam positions fell below the noise floor at approximately 12.5% of the expected scan positions for S. chuatsi and 22.2% for L. crocea. A 15° departure from broadside reduced the section-summed index by 3.73–11.43 dB. Kirchhoff-ray-mode (KRM) simulations based on post-thaw dual-view X-ray geometry were broadly consistent with the specimen-level contrast observed among the preserved specimens, but were 0.92–2.74 dB lower than the corresponding broadside section-summed measurement indices at 700 kHz. These differences are not a quantitative validation because the measured and modeled estimators, frequency weighting, geometry, and tissue parameters were not equivalent. These results demonstrate the feasibility of a calibrated beam-position workflow for preserved specimens, while not establishing live-fish target strength, species benchmarks, or biomass-estimation performance.

Monoterpenoid indole alkaloids from the aerial parts of Tabernaemontana divaricata (L.) R. Br. ex Roem. & Schult. and their anti-inflammatory activity and cytotoxicity on acute leukaemia cells - Wan-Qi Yang; Cai-Xia Wen; Er-Gu Chen; Ren-Feng Ye; Min Jiang; Gui-Guang Cheng; Ya-Ping Liu (Natural Product Research, 2026)

TCSwinPNet: a lightweight tri-branch convolutional Swin Transformer network with hybrid feature injection for Multispectral and panchromatic image fusion - Zechun Li; Xunqiang Gong; Xiong Xu; Yichuang Luo; Yuting Wan; Ailong Ma; Haiqin Cheng; Rong Liu; Yanfei Zhong (International Journal of Remote Sensing, 2026)

Real-world safety of aflibercept 8 mg in neovascular age-related macular degeneration - Wan-Ju Annabelle Lee; Daniel Hsiang-Te Tsai; Edward Chia-Cheng Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Corrigendum to “From fixed to condition-dependent emission factors: probabilistic tabular learning for wastewater N₂O inventories” [Water Research, Volume 304, 1 October 2026, 126371] - Jia-ji Chen; Hong-Cheng Wang; Wan-Xin Yin; Yu-Qi Wang; Jia-qiang Lv; Wen Wang; Ai-Jie Wang (Water Research, 2026)

Enhancing bi-directional wind energy harvesting via wake interference of micro-curved-surface bluff bodies - Lili Dong; Xudong Wang; Fayu Guo; Kai Xue; Guanggui Cheng; Wan Sun (Ocean Engineering, 2026)

Early fault warning for wind turbine main bearings using XGBoost and parameter-based transfer learning with SCADA data - Anping Wan; Wenbin Gong; Ting Chen; Khalil AL-Bukhaiti; Xiaomin Cheng; Xiaosheng Ji (Ocean Engineering, 2026)

Occupational health risks and abatement trade-offs of VOCs in key industries of the Yangtze River Delta: Insights for a shift from concentration-based compliance to reactivity- and toxicity-driven management - Xinglong Pang; Weichao Wu; Xujie Zhang; Jiachen Shen; Boyuan Zhang; Mei Wan; Mingjie Xie; Ping Cheng (Journal of Hazardous Materials, 2026)

Spatial metabolomic profiling of ripening pepper fruit (Capsicum annuum L.) by MALDI-MSI: Decoding metabolic heterogeneity and its role in quality attribute regulation - Yuanling Yang; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Food Chemistry, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

A spatiotemporally separated recognition–amplification strategy based on an M13 phage biological lever for immunodetection of bacteria - Chenlu Zhang; Fumei Cheng; Juanjuan Mou; Xiangyang Xiao; Xiaole Han; Li Zhang; Li Wang; Guoming Xie; Yushun Wan; Yujun Yang (Chemical Engineering Journal, 2026)

Copper stress responses in Scenedesmus obliquus–Bacillus subtilis Consortia: Machine Learning-Based prediction of copper removal - Dehua Zhao; Sze-Wan Poong; Wai Yan Cheah; Sai Hin Lai; Gek Cheng Ngoh; Tau Chuan Ling; Jo-Shu Chang (Bioresource Technology, 2026)

Innovative technologies and future perspectives in tumor microbiomics - Wan-Ting He; Xiaofang Xing; Fei Wang; Le Li; Ye Cheng; Gang Yao (Science China Life Sciences, 2026)

Tumorigenesis of well-differentiated and dedifferentiated liposarcoma: 12q amplicon architecture, oncogenic cargo, and evolutionary progression - Aobo Zhuang; Xiao Zhou; Chengfei Xu; YangJu Chen; Xueling Wang; Runchun Li; Jiajing Hu; Yinxue Cheng; Yunyan Wan; Ting Wu; Wengang Li (Cancer and Metastasis Reviews, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Iridoid constituents from the flower buds and inflorescences of Buddleja officinalis and their anti-pulmonary fibrosis activity - Xiao-Yu Yuan; Xue Gong; Shi-Ying Yuan; Wei-Jin Meng; Chen-Hao Yu; Shao-Jun Wang; Xiao-Tian Zhang; Jun-Cheng Su; Luo-Sheng Wan (Phytochemistry, 2026)

Motion-control parameter screening of underwater gliders under ocean thermal stratification: A trajectory-driven dynamic-thermal coupled framework - Xu Wan; Lianhong Zhang; Yan Liang; Yingjie Wang; Zhanzhan Miao; Shaoqiong Yang; Runfeng Zhang; Cheng Wang; Ming Yang; Wendong Niu (Ocean Engineering, 2026)

Swirling low-temperature plasma for phenolic wastewater degradation: Flow field regulation mechanisms and degradation pathway elucidation - Yihan Wang; Jiehui Ren; PuJing Yao; Tao Zhang; JiaYao Hui; Yao Pei; Tian Wan; Wen Cheng (Journal of Water Process Engineering, 2026)

An in-situ photoderivative fluorescence enhancement method without chromatographic separation for Aflatoxin B1 (AFB1) detection - Wan Tian; Wenhui Cheng; Chuanliang Wang; Jiashan Lu; Shihao Lu; Run Zhang; Yanxia Qi; Yafeng Guan; Xuhui Geng (Journal of Hazardous Materials, 2026)

Microbial fermentation of soybean meal generates low-molecular-weight peptides with enhanced antioxidant activity: Structural characterization, peptidomics, and in silico screening - Xiaohong Cheng; Yangling Wan; Yan Zheng; Xiaowei Zhang; Yapeng Fang (Innovative Food Science & Emerging Technologies, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

A hybrid mantle source for Chang’E-5 basalt: insights from ultra-trace element ratios of olivine - Cheng-Yu Du; Shao-Bing Zhang; Hejiu Hui; Ting Liang; Wan-Cai Li; Yong-Fei Zheng (Geochimica et Cosmochimica Acta, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

How Fe regulates adsorption and catalytic oxidation activity of Fe Mn Co-oxides for Mn2+ removal - Ya Cheng; Xiaoyang Cai; Xiangxuan Xing; Jianchao Zhao; Gang Wen; Qiqi Wan; Tinglin Huang (Desalination, 2026)

Enhanced utilization of okara through microbial fermentation: Isolation and immunostimulatory potential of a β-galactan - Yayuan Xu; Yanan Gao; Huiling Dong; Dongqi Li; Zhengyang Cheng; Yaqiong Wan; Xuanjun Wu; Jianghua Cheng (Carbohydrate Polymers, 2026)

3D gravity and magnetic joint inversion based on a double branch multi-channel CNN - Wan-cong Jiang; Yong-hui Zhao; Jin-yao Gao; Shuang-cheng Ge; Zhi-fei Xie (Applied Geophysics, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Synergistic catalytic oxidation of ammonia nitrogen in groundwater by iron-manganese oxide composites: Kinetics, mechanisms, and performance optimization - Ya Cheng; Yibo Wei; Biao Yang; Junfeng Wang; Gang Wen; Tinglin Huang; Qiqi Wan; Fenglin Wang (Journal of Environmental Chemical Engineering, 2026)

Litsea cubeba essential oil mitigates postharvest blueberry decay by damaging the cell barrier of Penicillium crustosum - Ruogu Cheng; Chunxiu Wan; Ziyu Wang; Jiao Hu; Xiumei Chen; Nengguo Tao; Xiaoli Tan (International Journal of Food Microbiology, 2026)

Labile Fe(III) species control arsenic adsorption and oxidation during magnetite-solution interactions under anoxic conditions - Xinyue Yu; Di Wu; Wan Cheng; Yuefei Ding; Xiaoxu Li; Jing Chen; Xiaohui Wu; Xin Zhang; Juan Liu; Linling Wang; Anxu Sheng; Kevin M. Rosso (Geochimica et Cosmochimica Acta, 2026)

TRIM37 promotes antibacterial defense by regulating antimicrobial peptides in Chinese mitten crab (Eriocheir sinensis) - Long-Teng Shen; Miao Zhang; Zi-Yi Chen; Zhi-Cheng Wan (Fish & Shellfish Immunology, 2026)

Predictive design of UV-curable bio-based polyurethane acrylate adhesives: Integrating viscoelasticity, adhesion, and controlled degradation - Bowen Xu; Weiyi Wang; Honghu Li; Gaoteng Shi; Hong Jiang; Chang Su; Shaoyu Wang; Tong Wan; Biao Wang; Bowen Cheng (Chemical Engineering Journal, 2026)

Corrigendum to “Dialdehyde xanthan gum and curcumin synergistically crosslinked bioprosthetic valve leaflets with anti-thrombotic, anti-inflammatory and anti-calcification properties” [Carbohydrate Polymers 310 (2023) 120724] - Mengyue Hu; Xu Peng; Shubin Shi; Chang Wan; Can Cheng; Xixun Yu (Carbohydrate Polymers, 2026)

Screening of Lead/Mercury-Tolerant Lactic Acid Bacteria, Development of a Probiotic Beverage from Auricularia auricula, Red Dates, and Nitraria Fruits, and Its Application for Lead Removal - Yingying Wang; Jieru Zhang; Lan Cheng; Yumeng Chang; Shuhong Ye; Huiping Wan; Xi Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Diversity of arbuscular mycorrhizal fungi of Taiwan cypress along altitude in tropical forests - Wan-Rou Lin; Hsuan-Min Cheng; Ren-Cheng Liu; Tzu-Chao Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2026)

Acidobacteria taxa mediate the biphasic temperature sensitivity of soil organic carbon in restored ecosystems - Man Cheng; Weiqi Feng; Minggang Xu; Shaoshan An; Lichao Fan; Katharina Maria Keiblinger; Shanping Wan; Zonglin Shi; Yongli Wen; Dong Liu (Applied Soil Ecology, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Molecularly engineered water oxidation sites in D–A conjugated polymers for efficient H2O2 photosynthesis in pure water - Chengming Li; Wang Wang; Jingzhao Cheng; Sijie Wan; Guoqiang Luo; Bei Cheng; Jingsan Xu; Shaowen Cao (Science Bulletin, 2026)

Division of labor in a synthetic consortium enables high-efficiency waxy oil biodegradation: Interfacial access provided by Bacillus unlocks deep degradation by Pseudomonas - Guangming Zhang; Yong Yang; Yanhong Zhao; Xiangqian Zhu; Wan Lei; Qiannan Yang; Haichen Li; Wei Cheng; Ning Mao; Yanmei Sun; Shiwei Wang (Journal of Hazardous Materials, 2026)

Mechanism of deep and selective sulfate removal from high-concentration CaCl2 solutions via porous interfacial deposition on calcium-modified carbon - Ghulam Mustafa; Zhe Zhang; Honggui Liu; Zhen Chen; Zihong Cheng; Cheng Yang; Shuqin Liu; Feilong Liang; Yong Guo; Guodong Wan; Niyazi Abulaizi; Wei Ma (Journal of Cleaner Production, 2026)

Effects of oxygen-fuel velocity ratio on soot formation and flame structure in CH4-CO2-O2 inverse diffusion flames - Teng Hu; Keyu Cheng; Huajie Lyu; Jun Wan; William L. Roberts; Chenghang Zheng; Peng Liu; Xiang Gao (Fuel, 2026)

Development and characterization of a liposome-based collagen delivery system with sustained release and preserved antioxidant activity - Helin Wan; Yiming Jiang; Shaojun Yun; Feier Cheng; Wenfei Zhao; Mengyang Liu; Jiayin Duan; Zhenrui He; Jinling Cao; Cuiping Feng (Food Chemistry, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Corrigendum to “Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review” [Sci. Total Environ., 864 (2023), 160990] - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2026)

Boosting the copper capture efficiency of charcoal for drinking water Depuration - Wu Xinyue; Nie Yudong; Wan Xingyue; Liu Jiaxin; Hou Cheng; Isaac A. Ololade; Emmanuel I. Unuabonah; Nurudeen A. Oladoja (Process Safety and Environmental Protection, 2026)

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Geochemical transformation of ferrihydrite: A review on mechanisms, effects of coexisting molecules and environmental implications - Yupeng YAN; Cheng WANG; Muammar MANSOR; Rui JIANG; Xiaoming WANG; Qin ZHANG; Xionghan FENG; Wenfeng TAN; Andreas KAPPLER; Biao WAN (Pedosphere, 2026)

Decoding the core microbiota during liquor fermentation of sauce-aroma baijiu: Advances in the characteristics of core microbial communities and their regulatory strategies - Cheng Wu; Xiuting Li; Bo Wan; Feng Hu; Jianfeng Hu; Hu Lu; Xi Chen; Weiwei Li; Diqiang Wang; Baoguo Sun (Food Research International, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Dynamic Modeling and Control of Floating Wind Turbine Platforms with a Gyroscopic Stabilizer - Ping Cheng; Tingyuan Zhang; Wenchuan Zhao; Decheng Wan (Journal of Marine Science and Engineering, 2026)
A gyroscopic stabilizer generates an anti-roll moment by regulating the precession angle of a high-speed rotor. By computing the precession-angle command in real time, the controller can effectively suppress roll motion. However, research on the application of gyroscopic stabilizers to floating wind turbines remains limited. In this study, the operating mechanism of a gyroscopic stabilizer is modeled, and frequency-domain stability analyses are conducted for the system dynamics both before and after the installation of the stabilizer. A pole-placement-based controller is designed to achieve active stabilization of wave-induced platform motions by adjusting the rotor precession angle. Based on wave spectrum analysis, numerical simulations are performed to compare system responses with and without the active controller under different sea conditions. The results demonstrate that the proposed anti-roll control strategy exhibits robust performance and can increase the roll reduction rate by at least a factor of two across a range of sea states. In addition, the anti-roll effectiveness is influenced by rotor speed and environmental conditions, with higher reduction rates achieved at higher rotor speeds, larger wave heights, and longer wave periods. In addition, we adopt a dual-gyro configuration to cancel yaw-interference moments, and the proposed controller is feedback-based (platform motion only), which is suitable for retrofit applications without requiring wave-preview sensors.

A review of transcriptional control and adaptive functions in terpenoid biosynthesis: Focus on MYB regulatory networks - Sihui Guan; Zhuping Yao; Chenxu Liu; Rongqing Wang; Meiying Ruan; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Plant Science, 2026)

Cytotype distribution and chloroplast phylogeography of Enkianthus chinensis complex, a mixed-ploidy species complex in subtropical China and adjacent areas - Hua Liang; Cheng Zhou; Wan Hu; Sujuan Wei; Dengmei Fan; Shuang Tian; Zhiyong Zhang (Perspectives in Plant Ecology, Evolution and Systematics, 2026)

An integrated hot air-microwave drying strategy for lignite: Achieving enhanced efficiency and CO2 reduction potential - Cheng Cheng; Mingqiang Gao; Zhenyong Miao; Keji Wan; Qiongqiong He (Journal of Cleaner Production, 2026)

Protein-selection mass spectrometry reveals novel RXRα-active chemicals in the Yangtze River and Yellow River - Cheng Xu; Geng Yue; Chenke Xu; Qiang Li; Xinming Shen; Kaisheng Hong; Yi Wan; Jianying Hu (Journal of Environmental Sciences, 2026)

Effect of sugar alcohol combined moist heat treatment on the physicochemical properties of glutinous rice flour - Jinling Li; Ning Zhang; Chuyun Wan; Zhan Wang; Cheng Guo; Weiping Jin; Wangyang Shen; Guoyan Yang (Journal of Cereal Science, 2026)

Design of Co(PO3)2@Ni3S4 core-shell heterojunctions for enhanced supercapacitor performance - Liu Wan; Cheng Du; Mingjiang Xie; Jian Chen; Yan Zhang (Chemical Engineering Journal, 2026)

Intraocular inflammation incidence and real-world safety of intravitreal faricimab treatment across retinal indications - Wan-Ju Annabelle Lee; Daniel Hsiang-Te Tsai; Shih-Chieh Shao; Edward Chia-Cheng Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Creation of high-performance two-dimensional nanocomposites by regulating voids - Sijie Wan; Zixuan Fang; Qunfeng Cheng (Science Bulletin, 2026)

Research on identification, functional characteristics, and applications of milk fat globule membrane proteins - Xiaoyu Ma; Yu Wan; Xingyu Bao; Jian He; Sufang Duan; Gang Feng; Haixia Wu; Shuzhen Cheng; Cong Wang (International Dairy Journal, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

Molecular sensomics reveal the cultivar dependence and seasonal dynamic mechanism behind the unique aroma of Wuyuan green tea - Cuinan Yue; Xiaoqun Xie; Meihong Yan; Luo Li; Sibin Wang; Yajing Wan; Dan Cheng; Lizhen Chen; Lifang Zou; Wenjin Li; Zhihui Wang (Food Chemistry, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

The relationship between environmental factors and forest fires in Taiwan: examining the increase in sudden dry months since 1991 - Li-Wei Lai; Wan-Li Cheng (Theoretical and Applied Climatology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Integrated transcriptomic and metabolomic analyses reveal the potential mechanisms underlying sex- and size-dependent resistance to Vibrio alginolyticus infection in the Chinese mitten crab (Eriocheir sinensis) - Rongchen Liu; Hui Wen; Xuguang Li; Jitao Zheng; Jinghao Hu; Hongyu Ren; Libao Wang; Yuchen Chen; Honglei Zhang; Huijun Gao; Weibing Guan; Yongxu Cheng; et al. (Aquaculture, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Wind-induced sloshing enhanced galloping energy harvesting based on phase adjustable bluff body-liquid interactions - Wan Sun; Ying Zhong; Zongyu Gan; Liang Yang; Guanggui Cheng; Zhongqiang Zhang (Ocean Engineering, 2026)

A case study on tropical cyclone Oma-induced phytoplankton bloom in eastern Australia - Yuxia Liu; Ye Wan; Ziqiong Cheng; Rufa'i Isyaku; Haibin Lü (Journal of Marine Systems, 2026)

Impact of PFOS on maternal and placental lipid metabolism and decreased placental vascularization in a murine model - Zheyu Cheng; Hin Ting Wan; Wing Yee Chan; Thomas Ka Yam Lam; Chris Kong Chu Wong (Journal of Hazardous Materials, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Flavor characteristics of traditional and mechanically processed base baijiu of sauce-flavor baijiu revealed by GC-IMS and GC-MS - Ruiqi Liu; Jialiang Niu; Bo Wan; Feng Hu; Cheng Wu; Junlin Yang; Anran Zhu; Baoguo Sun; Xiuting Li (Food Chemistry, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Efficient nitrogen removal in nitrite-dependent anaerobic methane oxidation biofilms and associated nitrogen and sulfur transformation pathways - Zhi-Cheng Zhao; Guo-Jun Xie; Xin Tan; Lu-Yao Liu; Cheng-Cheng Dang; Xiao-Wei Wang; Xuan Wang; Xin-Yu Wan; Ya-Song Chen; Wan Sun; Nan-Qi Ren (Chemical Engineering Journal, 2026)

Multifunctional polymeric mixed conductors via benzochalcogenodiazole heteroatom engineering enables high-performance and ultra-stable aqueous electrochemical devices - Chaoyue Chen; Junxin Chen; Donghao Li; Miao Xie; Guohong Hu; Runxia Wang; Jiaqi He; Shengyu Cong; Jiayao Duan; Wei Huang; Zhengke Li; Yuhua Cheng; et al. (Chemical Engineering Journal, 2026)

Transcriptional condensates enrich phosphorylated PRMT2 to stimulate H3R8me2a deposition and hypoxic response in glioblastoma - Feng Dong; Xuan Cheng; Jiaxiang Wan; Qian Li; Weijian Du; Wei Li; Xiaoyu Sun; Xudong Wu (Science China Life Sciences, 2026)

Biodiversity effects on ecological stability through ecosystem‐level feedback - Chun‐Wei Chang; Chih‐hao Hsieh; Maiko Kagami; Wan‐Hsuan Cheng; Takeshi Miki (Ecology, 2026)
Portfolio mechanisms are widely recognized as essential processes through which biodiversity promotes ecosystem stability. However, traditional theories often treat biodiversity as a static property, overlooking its dynamic nature, which is shaped by numerous ecosystem‐level processes identified since the 1950s. To address this gap, we develop a novel model framework grounded in island biogeography theory (IBT) to explore the ecosystem‐level mechanisms by which biodiversity and its dynamics influence ecosystem stability. This framework considers species diversity as a state variable, capturing its dynamical behavior driven by feedback mechanisms between species diversity, resource availability (nutrients), and the effects of diversity on multitrophic interactions within a plankton system. Specifically, our model demonstrates that phytoplankton diversity regulates the strength of plankton trophic interactions, which in turn alter plankton biomass and nutrient availability. These changes generate feedback loops that further reshape phytoplankton diversity itself. The presence of the feedback loops enhances the system's resistance to extinction: Increasing diversity promotes more efficient resource consumption when consumers face extinction risk, while declining diversity reduces resource consumption efficiency, thereby mitigating destabilization caused by consumer overgrazing. The critical role of species diversity dynamics in ecosystem stability is empirically supported by our analysis of a 30‐year phytoplankton dataset, which reveals a causal relationship between temporal variability in phytoplankton species richness and the stability of community biomass. Our findings unveil a new mechanism through which biodiversity influences ecosystem stability via ecosystem‐level processes, independently of population‐ or community‐level portfolio processes.

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Numerical investigation of mesh grouping effects on hydrodynamic force and twine tension in aquaculture nets under current and wave conditions - Zhiqiang Liu; Shaojian Guo; Rong Wan; Fuxiang Hu; Cheng Zhou (Ocean Engineering, 2025)

Hydrodynamic characterization and efficient prediction of tapered trash-blocking nets for coastal nuclear intakes: Integration of experiment, simulation, and machine learning - Shaojian Guo; Nan Gu; Cheng Zhou; Liwen Liu; Rong Wan; Yucheng Wang; Zhiqiang Liu (Ocean Engineering, 2025)

Enhanced removal of copper (Cu²⁺) by microalgae-bacteria consortium: Mechanistic insights, physiological responses, and artificial neural network (ANN)-based prediction - Dehua Zhao; Sze-Wan Poong; Tau Chuan Ling; Sai Hin Lai; Phaik-Eem Lim; Gek Cheng Ngoh (Journal of Environmental Chemical Engineering, 2025)

A hyper-crosslinked ionic polymer catalyzing CO2 one-pot two-step to dimethyl carbonate via HCO3-/OH- synergy - Jingya Yang; Ming Sun; Qinghua Qu; Jiquan Liang; Cheng Fang; Lei Wang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Unique ectomycorrhizal fungal association is a major conservation dilemma for the threatened ectomycorrhizal tree species - Ren-Cheng Liu; Wan-Rou Lin; Alija Bajro Mujic; Pi-Han Wang (Journal for Nature Conservation, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Air pollutants, temperature, and road traffic noise: their impact on chronic kidney disease incidence in older individuals in Taiwan - Ting-Yu Zhuang; Wan-Ju Cheng; Yun-Chieh Yang; Chih-Cheng Hsu; Ta-Yuan Chang (Environmental Research, 2025)

Sustainable renewable ammonia production via solar-driven biomass gasification: a techno-economic perspective - Hongbin Wan; Jingang Yao; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Weiming Yi; Jian Li; Lingyu Tai; Obie Farobie; Paolo De Filippis; Benedetta De Caprariis (Chemical Engineering Journal, 2025)

Construction of WS₂ photocatalytic membrane reactor (PMR) and the reaction intensification mechanism for dyes degradation - Li-Xin Song; Peng Cheng; Xin-Yu Cheng; Yan Chen; Xiao-Jing Guo; Wan-Zhong Lang (Chemical Engineering Journal, 2025)

Highly-microporous carbon created by mechanochemical recycling herbal waste for supercapacitor with superior energy density - Shufen Gan; Xingyan Xie; Liu Wan; Jian Chen; Cheng Du; Yan Zhang; Mingjiang Xie (Biomass and Bioenergy, 2025)

Tightly Interfaced Heterojunction of In2O3@TiO2: A Facile Synthesis of MOF-on-MOF Derived In2O3@TiO2 and their Enhanced Performance in Photodegrading Tetracycline Under Visible Light Irradiation - Xia Zhang; Mengqin Zhou; Xiu Wan; Xi Liu; Shixiong Hao; Chunru Cheng; Zhongming Xiao; Yongfan Wang (Water, Air, & Soil Pollution, 2025)

Integrated Physiological and Transcriptomic Analysis Reveals the Drought Stress Response Mechanisms in Chrysanthemum morifolium (Ramat.) Tzvel. ‘Boju’ - Tao Wang; Qian Shao; Min-yan Xu; Cheng Zhao; Lu Liu; Wen-tin Jiang; Qian-kun Han; Wan-yi Wang (Plant Molecular Biology Reporter, 2025)

The 1357 bp deletion in β-thalassemia: molecular profiling and hematological characterization in a Guangxi cohort - Youqiong Li; Tianjie Zhou; Lihua Ye; Liang Liang; Shufu Cheng; Lihong Zheng; Xi He; Peixing Wan; Tongfeng Huang (Molecular Biology Reports, 2025)

TICT-activated viscosity sensitive mitochondrial probes for imaging and early diagnosis of drug-induced liver injury - Jie Wang; Lifeiyang Wan; Kaiyuan Liu; Qi Su; Xinyue Zhao; Cheng Huang; Yunjia Zhao; Lei Hu; Hui Wang (Analytica Chimica Acta, 2025)

Identification and characterization of non-O1/O139 Vibrio cholerae isolated from farmed tadpoles of the black-spotted frog (Pelophylax nigromaculatus) - Meiping Huang; Xiaofang Zhou; Zhanpeng Chen; Kaihua Mei; Qingyun Yuan; Fengju Ding; Ankang Song; Yong Xiong; Cheng Jiang; Nan Chen; Xiaoling Wan (Antonie van Leeuwenhoek, 2025)

Promoting acetate production on the in situ reconstructed Cu nanoislands via pressure-regulated CO adsorption and electroreduction - Rongxing Qiu; Jiaran Li; Jiafeng Du; Siwang Zhang; Lingzhi Ding; Jinlong Wan; Cheng Li; Jinyu Ye; Jin-Chao Dong; Yuanjie Pang; Jian-Feng Li; Shuliang Yang; et al. (Science Bulletin, 2025)

A dimensionless prediction model for the dent depth of the inner pipe in a sandwich pipe - Haifeng Tian; Feng Guan; Feng Wan; Cheng Lv (Ocean Engineering, 2025)

Preparation and characterization of PAPP@MF microcapsules for enhancing the safety of PVDF - Long-Tai Qi; Lei Ma; Zhi-Xiang Xing; Ye-Cheng Liu; Wan-Zheng Lu; Han Han; Tian-Yu Zhou; Yao Wu (Journal of Fluorine Chemistry, 2025)

Analysis of nitrogen effects on starch characteristics of Japonica rice from northern China through flow cytometry - Bingchun Yan; Xuanming Wang; Yuqi Liu; Yuzhuo Liu; Min Zhong; Xue Wan; Ya Liu; Hongfang Jiang; Songting Liu; Huiling Liu; Qingchun Ma; Yanze Zhao; et al. (Food Chemistry, 2025)

Cinnamaldehyde nanoemulsion disrupts Listeria monocytogenes biofilms: Metabolomics reveals dual inhibition and removal mechanisms - Yurong Yang; Huayan Cheng; Qiujin Zhu; Jing Wan (Food Bioscience, 2025)

Tyramine injection enhances immune function and disease resistance in Penaeus monodon - Wan-Lin Tsai; Li-Yang Hsu; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2025)

Green manure species synergize with organic fertilization to enhance soil nutrient–microbial interactions and wheat productivity in oasis drip–irrigated systems - Liyang Cheng; Hao He; Shuai Li; Mengmeng Yu; Tingting Wan; Jie Qin; Chunyan Li; Junhua Li (Field Crops Research, 2025)

Finite strain solution for circular tunnels in strain-softening rock during its lifecycle based on unified strength theory - Xu-Guang Yu; Hong Zheng; Tao Wan; Shi-Cheng Li; Yu Liang (Computers and Geotechnics, 2025)

Single-stage reverse-structured solar evaporator from two to three dimensional by transparent hydrogel - Shen Du; Bing-Lin Bai; Ya-Ling He; Mingyun Dai; Jia-Cheng Wan (Chemical Engineering Journal, 2025)

Interface-engineered biochar catalysts functionalized with hydroxylamine-imidazolium ionic liquids for efficient CO2 fixation under ambient conditions - Yizhen Zou; Zhongwei Zou; Beiwen Wan; Lu Yu; Xinlian Li; Guoe Cheng; Hanzhong Ke (Chemical Engineering Journal, 2025)

Black phosphorus integrated self-assembled silk fibroin nanofibrous microspheres: Micro-hotbeds for accelerating bone regeneration - Jiangfeng Cai; Qichao Cheng; Chi Yan; Suting Zhong; Fang Lei; Yajun Shuai; Jie Wang; Zongpu Xu; Quan Wan; Chuanbin Mao; Mingying Yang (Chemical Engineering Journal, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Robust cobalt‑manganese nitride@nickel phosphide heterojunction cathode for long-cycle-life supercapacitors - Ziyan Zhang; Zhanhang Chen; Cheng Du; Yan Zhang; Jian Chen; Mingjiang Xie; Liu Wan (Chemical Engineering Journal, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

NMR-metabolomic analysis of banana (Musa acuminata) plants in response to λ-carrageenan treatment - Kah-Lok Thye; Dhilia Udie Lamasudin; Zetty Norhana Balia Yusof; Janna Ong-Abdullah; Wan-Hee Cheng; Intan Safinar Ismail; Kok-Song Lai (Acta Physiologiae Plantarum, 2025)

Conversion of α-linolenic acid into n-3 long-chain polyunsaturated fatty acids: bioavailability and dietary regulation - Lei Wang; Chen Cheng; Xiao Yu; Liang Guo; Xia Wan; Jiqu Xu; Xia Xiang; Jing Yang; Jingxuan Kang; Qianchun Deng (Critical Reviews in Food Science and Nutrition, 2025)

Estimating strong point CO2 emissions by combining spaceborne IPDA lidar and HSRL - Chonghui Cheng; Dong Liu; Shuaibo Wang; Xingying Zhang; Lu Zhang; Weibiao Chen; Jiqiao Liu; Xueping Wan; Wentai Chen; Xiaolong Chen; Jingxin Zhang; Jiesong Deng; et al. (Remote Sensing of Environment, 2025)

Ru-modified CoCr/WNb catalysts for the deep degradation of dichloromethane at low temperature - Pengfei Zhang; Shiyao Wang; Huanlong Cheng; Nengjie Feng; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging” [Food Res. Int. 206 (2025) 115973] - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Corrigendum to “Dynamic changes in volatile organic compounds of cherry tomato fruits during storage at different temperatures using HS-GC-IMS” [Food Res. Int. 218 (2025) 116790] - Sihui Guan; Fei Yang; Jinxiao Yao; Chaochao Liu; Rongqing Wang; Meiying Ruan; Zhuping Yao; Chenxu Liu; Hongjian Wan; Zhimiao Li; Ming Diao; Yuan Cheng (Food Research International, 2025)

Dynamic changes in volatile organic compounds of cherry tomato fruits during storage at different temperatures using HS-GC-IMS - Sihui Guan; Fei Yang; Jinxiao Yao; Chaochao Liu; Rongqing Wang; Meiying Ruan; Zhuping Yao; Chenxu Liu; Hongjian Wan; Zhimiao Li; Ming Diao; Yuan Cheng (Food Research International, 2025)

Corrigendum to “Analysis of nitrogen effects on starch characteristics of Japonica rice from northern China through flow cytometry” [Food Chem. 492(Part 1) (2025) 145344] - Bingchun Yan; Xuanming Wang; Yuqi Liu; Yuzhuo Liu; Min Zhong; Xue Wan; Ya Liu; Hongfang Jiang; Songting Liu; Huiling Liu; Qingchun Ma; Yanze Zhao; et al. (Food Chemistry, 2025)

Salmon leather collagen peptide alleviates UVA-induced photoaging via Nrf2/Keap1 pathway by enhancing antioxidant defense and preserving skin elasticity - Baifeng Fu; Yu Wan; Xiaoyu Ma; Zhihui Chang; Ximing Yang; Xinran Liu; Haixia Wu; Shuzhen Cheng; Ming Du (Food Bioscience, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Enhanced oxidative removal of ammonia from groundwater: Unveiling the superior performance, kinetics, and mechanisms of ferric aluminate inorganic gel-strengthened iron/manganese oxide-loaded filter media - Zikang Xiong; Biao Yang; Junfeng Wang; Ya Cheng; Gang Wen; Tinglin Huang; Qiqi Wan; Fenglin Wang (Chemical Engineering Journal, 2025)

Hierarchical mesh-interpenetrating PEGDE-LC composite solid electrolyte for high-performance lithium metal batteries - Yongquan Zhang; Jingrun Hu; Jingshun Wang; Sen Wang; Cheng Wan; Yue Zhang; Tiandong Zhang; Changhai Zhang; Qingguo Chi (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Ferrous activated sodium percarbonate for controlling sulfide and methane production in sewer sediment - Hong-Xu Bao; Wan-Xin Yin; Shuai Liu; Jiaqiang Lv; Jiaji Chen; Hong-Cheng Wang; Ai-Jie Wang (Bioresource Technology, 2025)

A Lactobacillus Combination Ameliorates Lung Inflammation in an Elastase/LPS—induced Mouse Model of Chronic Obstructive Pulmonary Disease - Huan-Ting Shen; Yi-Ting Fang; Wan-Hua Tsai; Chia-Hsuan Chou; Ming-Shyan Huang; Yao-Tsung Yeh; Jiun-Ting Wu; Cheng-Hsieh Huang; Bing-Yen Wang; Wen-Wei Chang (Probiotics and Antimicrobial Proteins, 2025)
Chronic obstructive pulmonary disease (COPD) is the world's leading lung disease and lacks effective and specific clinical strategies. Probiotics are increasingly used to support the improvement of the course of inflammatory diseases. In this study, we evaluated the potential of a lactic acid bacteria (LAB) combination containing Limosilactobacillus reuteri GMNL-89 and Lacticaseibacillus paracasei GMNL-133 to decrease lung inflammation and emphysema in a COPD mouse model. This model was induced by intranasal stimulation with elastase and LPS for 4 weeks, followed by 2 weeks of oral LAB administration. The results showed that the LAB combination decreased lung emphysema and reduced inflammatory cytokines (IL-1β, IL-6, TNF-α) in the lung tissue of COPD mice. Microbiome analysis revealed that Bifidobacterium and Akkermansia muciniphila , reduced in the gut of COPD mice, could be restored after LAB treatment. Microbial α-diversity in the lungs decreased in COPD mice but was reversed after LAB administration, which also increased the relative abundance of Candidatus arthromitus in the gut and decreased Burkholderia in the lungs. Furthermore, LAB-treated COPD mice exhibited increased levels of short-chain fatty acids, specifically acetic acid and propionic acid, in the cecum. Additionally, pulmonary emphysema and inflammation negatively correlated with C. arthromitus and Adlercreutzia levels. In conclusion, the combination of L. reuteri GMNL-89 and L. paracasei GMNL-133 demonstrates beneficial effects on pulmonary emphysema and inflammation in experimental COPD mice, correlating with changes in gut and lung microbiota, and providing a potential strategy for future adjuvant therapy.

Vismodegib Potentiates Marine Antimicrobial Peptide Tilapia Piscidin 4-Induced Cytotoxicity in Human Non-Small Cell Lung Cancer Cells - Wei-Chen Yeh; Yun-Chieh Tu; Tzu-Cheng Chien; Pei-Ling Hsu; Chu-Wan Lee; Shih-Ying Wu; Bo-Syong Pan; Hsin-Hsien Yu; Bor-Chyuan Su (Probiotics and Antimicrobial Proteins, 2025)

Modeling and simulation of steam-enhanced extraction: Parameter effect of injected steam-air mixture on NAPL remediation at contaminated sites - Zhiwei Dong; Zhisong Ou; Yong Wan; Zhenxiang Su; Zhirun Xia; Xiang Sun; Fanbao Cheng; Lei Liu; Zhixiang Chen; Qiang Xue (Journal of Hazardous Materials, 2025)

Growth-promoting bacterium Enterobacter sp. CS8-gfp triggers jasmonate signaling pathway for atrazine and thiamethoxam degradation in rice (Oryza sativa L.) - Li Ya Ma; Qun Wan; Jing Ge; Yong Li; Fayun Feng; Mei Li; Jinjin Cheng; Jian Chen; Ya Wang; Yaoyao Cao; Chenye Yang; Xiangyang Yu (Journal of Cleaner Production, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Explosive growth characteristics of 5.6–560 nm particles and deposition in human respiratory during spring in Yangtze River Delta region, China - Yingru Gong; Jinping Ou; Qihou Hu; Chengzhi Xing; Yizhi Zhu; Yuhui Wan; Danni Wang; Chao Zhang; Lixin Guan; Jiaxuan Feng; Xiangguang Ji; Xinqi Wang; et al. (Journal of Environmental Sciences, 2025)

Navigating crowds: Reconsidering visitor recreational experience and crowding preference for a forest park in Taiwan - Wan-Yu Liu; Chin-Chun Yen; Rachel S.K. Lee; Chun-Cheng Lin (Forest Policy and Economics, 2025)

A flexible and efficient UNITID-based access control (UBAC) model for environmental monitoring data - Jinku Huang; Changxiu Cheng; Bin Li; Yang Gao; Ping Li; Jiawei Wan; Jadunandan Dash (Environmental Modelling & Software, 2025)

A programmed Ca2+ nanomodulator by dynamically regulating autophagy and neuroinflammation for Parkinson's disease therapy - Wengui Lu; Chuan Zhang; Yaru Zhang; Ru Xiao; Chaoqi Wei; Fan Zhang; Zhenbao Li; Hewan Xia; Mimi Wan; Zhifei Cheng; Qi Wang (Chemical Engineering Journal, 2025)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Programmable filler alignment via dynamic covalent polymer networks: Mechanically robust and sensitive doped sensors for human motion monitoring - Qianjun Yin; Fushan Guo; Yi Zhao; Xinyi Liu; Tong Wan; Biao Wang; Shaoyu Wang; Bowen Xu; Bowen Cheng (Chemical Engineering Journal, 2025)

Feasibility and Optimization Conditions for Enhancing Dewatering Efficiency of Residual Sludge in a Citrate-Fe(II) Activated Persulfate System - Xiaoyan Liu; Tian Wan; Wen Cheng; Jingxin Sun; Jiehui Ren; Min Wang (Water, Air, & Soil Pollution, 2025)

Urban Flood Inundation Area Detection using YOLOv8 Model - Fengchang Xue; Yannian Cheng; Yufang Shen; Jianfei Chen; Jiaquan Wan (Water Resources Management, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Individual Fish Broadband Echo Recognition Method and Performance Analysis Oriented to Aquaculture Scenarios - Hang Yang; Jing Cheng; Guodong Li; Shujie Wan; Jun Chen (Fishes, 2025)
Obtaining the echo of individual fish is an important prerequisite for fisheries acoustic applications, such as in situ measurement of fish target strength and assessment of fish abundance using the counting method. It is also the foundation for evaluating the growth status of farmed fish and managing aquaculture risks. The density of farmed fish populations is typically higher, and such high-density aquaculture further increases the difficulty of obtaining individual fish echoes in practical applications. Building upon previous research and considering the behavioral characteristics of fish in aquaculture settings, this study conducted performance simulations, live fish experiments in simulated aquaculture cages, and comparative evaluations of three individual fish broadband echo detection methods based on a broadband signal system: the amplitude pulse width method (APM) based on echo envelopes, the peak detection and time delay estimation method (PDM), and the peak time delay combined with instantaneous frequency method (PDIM). This study assumed a dorsolateral fish orientation, which limits its research scope and applicability. The results showed that the PDIM achieved a detection accuracy of 78.34% and a false recognition rate of 1.32%. The APM based on echo envelopes was insensitive to individual fish echoes and had lower recognition accuracy. The PDM exhibited better individual fish echo capture capabilities, while the PDIM demonstrated superior overlapping echo rejection capabilities.

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Data-driven early fire detection in offshore wind turbines: A TCN-ECA based approach leveraging SCADA data - Anping Wan; Wenbin Gong; Khalil AL-Bukhaiti; Xiaomin Cheng; Xiaosheng Ji; Yunsong Ji; Shidong Ma (Process Safety and Environmental Protection, 2025)

Mechanism-embedded graph neural network for predicting and interpreting methane and sulfide production in sewers - Hong-Xu Bao; Wan-Xin Yin; Shuai Liu; Jia-Qiang Lv; Jia-Ji Chen; Hong-Cheng Wang; Ai-Jie Wang (Journal of Water Process Engineering, 2025)

Risk assessment of hydrological drought in water-donating and water-receiving areas of an inter-basin water diversion project - Junde Wang; Wan Zhou; Dedi Liu; Yufei Cheng (Journal of Environmental Management, 2025)

Construction and analysis of atmospheric visibility and fog-haze datasets in China (2001−2023) based on machine learning models - Haifeng Xu; Wenhui Luo; Jinji Ma; Bing Dong; Cheng Wan; Shijie Zhao; Cheng Dai; Rui Qian; Zhengqiang Li (Atmospheric Research, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Mechanism of Drilling Parameter Distortion Induced by Drill Rod Buckling While MWD Application - Xin Sun; Jingyi Cheng; Xianxin Zhang; Zhijun Wan; Yadong Lian; Kechen Liu (Rock Mechanics and Rock Engineering, 2025)

Impact of Clay Minerals on the Characteristic Strength and Nonlinear Dissipative Energy Modeling of Water-Saturation Mudstone - Yugang Cheng; Rui Wu; Bo Hu; Mengru Zeng; Yong Zhao; Gexin Wan; Xuefu Zhang; Jinjie Yang (Rock Mechanics and Rock Engineering, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Effects of Lead Stress on Seed Germination and Seedling Growth of Ten Afforestation Trees in Arid Regions - Nan Yang; Yuan Cai; Cheng Wan; Furong Zhou; Yue Wang (Forest Science, 2025)

Biodiversity Consistently Promotes Ecosystem Multifunctionality Across Multiple Temporal Scales in an Aquatic Microbial Community - Wan‐Hsuan Cheng; Takeshi Miki; Chao‐Chen Lai; Fuh‐Kwo Shiah; Chia‐Ying Ko; Chih‐hao Hsieh; Chun‐Wei Chang (Ecology Letters, 2025)
Biodiversity is essential for sustaining ecosystem multifunctionality (EMF), yet its role in natural ecosystems remains uncertain because various environmental drivers, alongside biodiversity, influence EMF, complicating the empirical biodiversity–EMF relationship. Additionally, the effects of biodiversity and environmental drivers on EMF likely vary across temporal scales, making this relationship inherently scale‐dependent. Over nine years, we conducted a biweekly sampling, measuring microbial diversity, EMF (via 31 carbon utilisation functions), and various environmental variables in a subtropical freshwater ecosystem. Our analysis across inter‐annual, seasonal, and short‐term scales revealed that biodiversity consistently enhances EMF at all scales, while environmental drivers such as precipitation, temperature, and phosphate influenced EMF only at specific scales (short‐term, seasonal, and inter‐annual, respectively). Importantly, biodiversity mediated these environmental impacts, reinforcing its central role in maintaining EMF. These findings highlight biodiversity as a critical pillar for EMF across scales, underscoring the importance of conserving biodiversity to sustain EMF amid multifaceted environmental changes.

Bacterial pathogen assemblages on microplastic biofilms in coastal waters - Linus Shing Him Lo; Ruka Mei Kwan Tong; Wan Chan; Wingkei Ho; Jinping Cheng (Marine Pollution Bulletin, 2025)

Exploring the influence of carbon source on extracellular polymeric substances, nitrogen metabolic pathways and electron transfer during nitrogen biodegradation - Jiayao Hui; Jiehui Ren; Wen Cheng; Yao Pei; Min Wang; Tian Wan (Process Safety and Environmental Protection, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Preparation and properties of esterified starch-based antimicrobial sustained-release indicator films - YiNing Xu; Cheng Tang; Peng Zhang; YingLan Yuan; ShiYan Zhou; JinMing Wan; Zhihe Qing; Qi-Jie Chen (Food Research International, 2025)

The history of the Tsushima Warm Current since the middle Miocene: Co-evolution with the Kuroshio Current and the Western Pacific Warm Pool - Yulong Cheng; Shiming Wan; Rebecca S. Robinson; Kenji M. Matsuzaki; Debo Zhao; Xingyan Shen; Lina Zhai; Yi Tang; Huiling Liu; Anchun Li (Earth and Planetary Science Letters, 2025)

Different Expression Patterns and Interactions with Time Recorder DAL1 Revealed the Gene Expansion and Functional Differentiation of Flowering Integrator SOC1 During Larch Aging - Zha-Long Ye; Xiang-Yi Li; Dong-Xia Cheng; Wan-Feng Li (Journal of Plant Growth Regulation, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Ecosystem Shifts and Cladocera Responses in a Freshwater Lake in Semi‐Arid Regions: The Successional Synergistic Effects of Natural and Human Factors in the Past 170 Years - Longjuan Cheng; Bin Xue; Jinliang Liu; Xiangzhen Kong; Can Zhang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Wenxiu Zheng (Journal of Biogeography, 2025)
Aim Freshwater lake ecosystems in semi‐arid regions are highly fragile and complex. However, the driving forces behind changes in temperate lake ecosystems at a regional scale in China remain largely unclear, primarily due to the lack of multidecadal to centennial regional studies. This study focuses on Hulun Lake, the largest freshwater lake in northern China's semi‐arid region, with the aim of elucidating the characteristics and driving mechanisms of freshwater lake ecosystems in such areas. Location Hulun Lake, the largest freshwater lake in northern China's semi‐arid region (48.55° ~ 49.33° N, 116.97° ~ 117.81° E). Time Period From the 1840s to 2010s AD. Major Taxa Studies Zooplankton Cladocera. Methods High‐resolution multiproxy palaeoecological data (including biological and geochemical indices), human activities parameters and observational datasets from the lake basin are used to explore ecosystem shifts and Cladocera responses in Hulun Lake, located in a semi‐arid region, over the past 170 years. The hypothesis that changes in the zooplankton Cladocera community composition within the ecosystem are driven by synergistic interactions among multiple factors was tested using effective approaches based on generalised additive models (GAM) and redundancy analysis (RDA). Results The results indicate that both internal factors (such as lake sedimentary environment, fish catches, lake water level, organic matter and nutrients) within the lake and external factors (including population, urbanisation rate and livestock husbandry) in the surrounding basin have been key drivers influencing the structure of Cladocera in Hulun Lake over the past 170 years. The originally predominant littoral Cladocera species ( Chydorus sphaericus . sl.) were replaced by planktonic (Bosminidae) since the 1980s accompanied by a decline in diversity, which corresponds with the process of eutrophication and pollution in the lake. Main Conclusions The dynamics of the Cladocera assemblages indicate that the lake ecosystem is vulnerable to further imbalance since the 2000s due to the ongoing synergistic effects of declining fishery catches, increasing livestock numbers, rising populations, urbanisation rates and declining water levels in semi‐arid regions.

Mineral types dominate microbiomes and biogeochemical cycling in acid mine drainage - Ye Huang; Xiu-Tong Li; Zhen Jiang; Zong-Ling Liang; Wan Liu; Zheng-Hua Liu; Liang-Zhi Li; Zhen-Ni Yang; Guo-Qing Zhang; Hua-Qun Yin; Jie-Liang Liang; Nan Zhou; et al. (Water Research, 2025)

Interpretable machine learning prediction of visits for respiratory diseases in Lanzhou, China: impact of air pollution and meteorological variables - Yuxia Ma; Wanci Wang; Zongrui Liu; Yuhan Zhao; Ziyue Wan; Pengpeng Qin; Bowen Cheng (Urban Climate, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Microalgae as a sustainable source of carotenoids: Strategies to improve yield and productivity - Wan Adibah Wan Mahari; Wan Aizuddin Wan Razali; Yoong Kit Leong; Vishal Sharma; Vaibhav Sunil Tambat; Himanshu K. Pathak; Nyuk Ling Ma; Siew-Moi Phang; Cheng-Di Dong; Su Shiung Lam (Journal of Environmental Chemical Engineering, 2025)

Dihydroxy functionalized binuclear carbonate based poly(ionic liquid)s for highly efficient conversion of low-concentration CO2 into cyclic carbonate - Yuqiao Jiang; Xinyu Yuan; Peiru Wang; Linyan Cheng; Ranran Li; Qinghua Qu; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Explosion characteristics of non-premixed cloud in relative motion between heat source and flowing cloud - Hangwei Wan; Qi Zhang; Yuquan Wen; Cheng Wang (Fuel, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Enhancing denitrifying anaerobic methane oxidation for nitrogen removal with low-temperature biochar - Wei Chong; Shaohua Wang; Jiaxin Cheng; Xue Lou; Xuebao Wan; Xiangyu Sun; Mingyang Wang; Shaoping Kuang; Hui Chen; Shuai Liu (Bioresource Technology, 2025)

Prediction Methods for Antimicrobial Resistance Trends in China - Zhengyang Wu; Ning Zhang; Bohan Zhang; Haiwei Wang; Jiaqi Yan; Xingyu Wan; Ming Cheng; Junming Bu; Yinan Du (Indian Journal of Microbiology, 2025)

Inverse differential equation modeling of ENSO prediction based on memory kernel functions - Shiquan Wan; Zhikuan Wang; Hongjia Lei; Lingzhi Zhang; Xintong Zhao; Shasha Xu; Mengsheng Qin; Yuan Cheng; Qianrong Ma (Climate Dynamics, 2025)

Provenance of Upper Jurassic in North Yellow Sea Basin, Eastern North China Craton - Haitian Yu; Zhongjie Xu; Rihui Cheng; Duo Wan; Dan Gao; Zhen Zhang (Journal of Earth Science, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

A New Species of Fur Mite (Acari: Myobiidae) Parasitizing Laboratory Mice, With a Key to the Subgenus Myobia - Ying-Chien Cheng; Jhih-Rong Liao; Cho-Hua Wan (Acta Parasitologica, 2025)

Interannual variability of Indo-Pacific humpback dolphin (Sousa chinensis) habitats in the Eastern Pearl River Estuary, China - Shujie Wan; Guodong Li; Yutao Zhang; Jing Cheng; Hang Yang (Frontiers in Marine Science, 2025)
Quantifying and analyzing the temporal and spatial variations of cetacean habitats is essential for establishing marine protected areas and preserving natural cetacean populations. Despite its importance, studies focusing on the interannual variability of cetacean habitats remain scarce. This study analyzed sighting records of Sousa chinensis and sea surface temperature (SST) data in the eastern Pearl River Estuary (PRE) from 2009 to 2022. Initially, the spatiotemporal variations in sighting effort and their correlation with SST were examined. Subsequently, the Suitability Index (SI) model was applied to calculate the distribution of S. chinensis habitats across different years and to assess interannual changes in habitat distribution in relation to climate change. The findings revealed that S. chinensis sightings were concentrated within a 227 km² area surrounding Lantau Island in the eastern PRE. The SST where sightings occurred ranged from 15.9°C to 29.8°C, with a strong positive correlation (r = 0.74, P <0.05) between sighting effort and SST. The SI model effectively identified habitat distribution patterns across years, highlighting a continuous decline in the area of suitable habitats (SI ≥ 0.6) from 2009 to 2022. The largest suitable habitat area was recorded in 2012 (a neutral year), while the smallest was observed in 2020 (a La Niña year). During ENSO events, suitable habitats exhibited a northward shift in average latitude. This study introduces novel methodologies for S. chinensis habitat research, supports the development of more effective monitoring strategies, and provides valuable insights for the establishment of marine protected areas.

The strengthening effects of different types of salt on the mechanical properties of soy protein isolate and pea protein isolate composite gels - Yujie Lei; Jin Yue; Tiantian Min; Chuanxiang Cheng; Shihan Weng; Yangyang Long; Yuwan Luo; Yan Zheng; Yangling Wan (Food Hydrocolloids, 2025)

Unveiling the functional heterogeneity of endogenous tissue extracellular vesicles in skeletal muscle through multi-omics - Yizhuo Wang; Peng Lou; Xiyue Zhou; Yijing Xie; Yimeng Zhang; Shuyun Liu; Lan Li; Yanrong Lu; Meihua Wan; Jingqiu Cheng; Jingping Liu (Chemical Engineering Journal, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

A Highly Selective and Sensitive Turn-on Fluorescent Probe for Al3+ Detection: Properties and Applications - Xiao-Yu Li; Hang-Yu Xie; Neng Wan; Xiao-Dong Ning; Hao-Tong Li; Qing-Zhong Li; Yu-Guang Fan; Xin Qiao; Cheng-Zhi Xie (Journal of Fluorescence, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Corrigendum to “High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle” [Meat Science volume 220 (2025) 109693] - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Determination of five alternaria toxins in peppermint by dispersive solid-phase extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry based on MOF-808-TFA - Minhai Liu; Yan Zhang; Rui Cheng; Ting Tan; Lan Guo; Fan Liu; Yiqun Wan (Food Chemistry, 2025)

Quantitative microbial risk assessment for on-site employees in a wastewater treatment plant and implicated surrounding residents exposed to S. aureus bioaerosols - Wei-di Wan; Jia-xin Ma; Tian-nuo Lai; Yong-tang Yan; Wajid Ali; Zhen Hu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Protecting mud crabs from pollution by microplastics, per- and polyfluoroalkyl substances, polycyclic aromatic hydrocarbons, pesticides, and heavy metals in mangroves - Wan Adibah Wan Mahari; Yiu Fai Tsang; Che-Jung Hsu; Hanafiah Fazhan; Youji Wang; Kianann Tan; Rock Keey Liew; Cheng-Di Dong; Khor Waiho; Su Shiung Lam (Environmental Chemistry Letters, 2025)

Visible light-driven triazine-based S-scheme COF-TpTt@BiOBr heterojunction with oxygen vacancy for enhanced photocatalytic pollutants removal and hydrogen production - Qingmei Tang; Yuqi Wan; Zhiquan Pan; Qingrong Cheng (Environmental Research, 2025)

Estimation of regional PM2.5 concentration in China based on fine-mode aerosol optical thickness (AODf) and study of influencing factors - Cheng Wan; Haifeng Xu; Wenhui Luo; Jinji Ma; Zhengqiang Li (Atmospheric Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Mechanochemically coordinating Fe-tannic acid towards the fabrication of highly-microporous carbon as advanced supercapacitor electrode - Yue Liu; Bei Cheng; Xingyan Xie; Jian Chen; Liu Wan; Cheng Du; Yan Zhang; Mingjiang Xie (Fuel, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

Optimization of Configuration Design for Underwater Dam Defect Detection Vehicles - Hong-Xia Cheng; Mei-Jie Cao; Peng-Fei Xu; Yan Kai; Zi-Peng Wang; Gang Wan; Qiao Hu (Journal of Marine Science and Engineering, 2025)
Hydropower stations and dams play a crucial role in water management, ecology, and energy. To meet the requirements of underwater dam defect detection, this study develops a streamlined underwater vehicle design and operational framework inspired by bionic principles. A parametric modeling approach was employed to propose the vehicle’s streamlined configuration. Using CFD simulations, hydrodynamic coefficients were calculated and validated through towing experiments in a pool. The hydrodynamic stability of the vehicle was assessed and verified through these analyses. Additionally, various configurations were generated using a free deformation method. An optimization function was established with resistance and stability as the objectives, and the optimal result was derived based on the function’s calculation outcomes. The study designed a high-metacentric underwater vehicle, inspired by the seahorse’s shape, and introduced a novel stability evaluation method. Simulations were conducted to analyze the vehicle’s variable attack angle, drift angle, pitching, and rotational motion at a forward three-throttle speed. The results demonstrate that the vehicle achieves static stability in both the horizontal and vertical planes, as well as dynamic stability in the vertical plane, but exhibits limited dynamic stability in the horizontal plane. After optimizing the original configuration, the forward resistance was reduced by 2.15%, while the horizontal plane dynamic stability criterion CH was improved by 35.29%.

New quantified climate reconstruction in southern China suggests a potential influence of winter cloud cover across East Asia during the Holocene - Xiao Zhang; Cong Chen; Kexin Wang; Meihuan Li; Yuanfu Yue; Jun Cheng; Mengna Liao; Kai Li; Lina Liu; Zhanghua Wang; Rachid Cheddadi; Qiuchi Wan; et al. (Science of The Total Environment, 2025)

Ordered self-assembled monolayer improved the buried interface of wide bandgap perovskite for efficient and stable semi-transparent solar cells - Peiran Hou; Shenghan Hu; Yuxi Zhang; Junye Pan; Min Hu; Jiahui Chen; Bingxin Duan; Li Wan; Pin Lv; Yanqing Zhu; Shengqiang Xiao; Yi-Bing Cheng; et al. (Chemical Engineering Journal, 2025)

Microbial-Guided prediction of methane and sulfide production in Sewers: Integrating mechanistic models with Machine learning - Wan-Xin Yin; Jia-Qiang Lv; Shuai Liu; Jia-Ji Chen; Jun Wei; Cheng Ding; Ye Yuan; Hong-Xu Bao; Hong-Cheng Wang; Ai-Jie Wang (Bioresource Technology, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Evaluating the impact of dermal absorption on internal doses of dechlorane plus in Chinese e-waste recycling employees - Yao-Yuan Wan; Xiao-meng Cheng; Xing-Hong Li; Feng-Shuang Wang; Yuan-Yuan Li; Jing Li; Zhan-Fen Qin (Chemosphere, 2024)

Effects of material and structure types on drifting speed of fish aggregation devices (FADs) in tuna purse seine fishery - Yucheng Wang; Cheng Zhou; Rong Wan; Liuxiong Xu; Shaojian Guo (Marine Pollution Bulletin, 2024)

Water pollutant cadmium-induced intestinal inflammation in Eriocheir sinensis and potential therapeutic drugs - Yana Cheng; Chao Li; Yue Chen; Huan Liu; Haifu Wan; Xianjiang Kang; Shuai Guo (Science of The Total Environment, 2024)

Occurrence, sources, and human exposure assessment of amine-based rubber additives in dust from various micro-environments in South China - Chenglin Liu; Sheng Wan; Yao Cheng; Zhong Lv; Shusheng Luo; Yuge Liang; Yichun Xie; Xinrui Leng; Min Hu; Bintian Zhang; Xin Yang; Guomao Zheng (Science of The Total Environment, 2024)

Design and modeling of an eco-friendly anchored fish aggregating device with artificial reef subjected to wave and current - Tongzheng Zhang; Wenhua Zhao; Cheng Zhou; Fenfang Zhao; Rong Wan (Ocean Engineering, 2024)

The novel prognostic analysis of AML based on ferroptosis and cuproptosis related genes - Mei Wu; Anan Li; Tingting Zhang; Weirong Ding; Yujing Wei; Caishui Wan; Bo Ke; Hongbo Cheng; Chenghao Jin; Chunfang Kong (Journal of Trace Elements in Medicine and Biology, 2024)

Influence of oxygen transfer performance on nitrogen metabolism and microbial community structure in an aerobic fluidized bed biofilm reactor under different aeration aperture - Xiaoyan Liu; Jiehui Ren; Wen Cheng; Jiayao Hui; Tian Wan (Journal of Environmental Chemical Engineering, 2024)

A comprehensive review of critical factors affecting green ammonia synthesis by electrochemical process - Cheng-Yi Li; Shen-Wei Chu; Chia-Yun Ho; Han-Jung Chang; Terng-Jou Wan (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to ‘A facile synthesis of Ag3PO4/BiPO4 p-n heterostructured composite as a highly efficient photocatalyst for fluoroquinolones degradation’ [Environ. Res. 203 (2022) 111843] - Xin Zhu; Yu Yan; Yuting Wang; Tao Long; Jinzhong Wan; Cheng Sun; Yang Guo (Environmental Research, 2024)

Methylparaben changes the community composition, structure, and assembly processes of free-living bacteria, phytoplankton, and zooplankton - Man Wang; Shengxing Wang; Huabing Li; Zhendu Mao; Yiwei Lu; Yunshan Cheng; Xiaotong Han; Yujing Wang; Yanru Liu; Shiqiang Wan; Li-Jun Zhou; Qinglong L. Wu (Environmental Research, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Analysis of chitinase gene family in barley and function study of HvChi22 involved in drought tolerance - Kui Wan; Sebastian Buitrago; Bingyun Cheng; Wenying Zhang; Rui Pan (Molecular Biology Reports, 2024)

Association of Fusobacterium nucleatum infection with the clinicopathological characteristics in colorectal cancer patients - Siew-Wai Pang; Subasri Armon; Jack Bee Chook; Jactty Chew; Kaik-Boo Peh; Wendy Wan-Dee Lim; Suat Cheng Peh; Sin-Yeang Teow (Molecular Biology Reports, 2024)

Paenibacillus lacisoli sp. nov., a mesotrione-degrading strain isolated from lakeside soil - Qimiao Xu; Bin Liu; Yingying Wan; Xueting Jiang; Le Chen; Dongmei Mao; Gang Chen; Dan Cheng; Jian He; Qirong Shen (Antonie van Leeuwenhoek, 2024)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Effects of microwave treatment on vegetable oil quality & biological activities - Fuchun Chen; Ben Xu; Wenyu Cui; Yunfu Wang; Fachun Wan; Anwei Cheng (Trends in Food Science & Technology, 2024)

Co-abatement of greenhouse gas and air pollutants in Shanghai, China: Spatial hotspots identification, effects assessment and policy implication - Xiahong Shi; Zining Huang; Qizhen Liu; Yi Fang; Wenjie Wan; Jinping Cheng (Science of The Total Environment, 2024)

Evaluating the hydrodynamic characteristics and shape configuration of fine-mesh nettings for sampling nets - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Tongzheng Zhang; Yucheng Wang; Shaojian Guo; Cheng Zhou (Ocean Engineering, 2024)

Longitudinal and transversal intramuscular variation of muscle fiber and meat quality characteristics in bovine M. longissimus thoracis et lumborum - Junyoung Park; Chang Wan Sun; Sumin Song; Huilin Cheng; Choeun Im; Teak Soon Shin; Gap-Don Kim (Meat Science, 2024)

Spontaneous imbibition in hydrate-bearing sediments under creep - Kailun Wang; Gang Lei; Jiangtao Qu; Yang Wu; Wan Cheng; Jiadi Tang; Yuyi Lu (Gas Science and Engineering, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

A gradient nanoporous radiative cooling ceramic with high spectral selectivity - Xinfei Wang; Dongqing Liu; Zhongyixin Wan; Zi Wang; Jinshan Yu; Haifeng Cheng; Yan Jia; Tingting Shi (Chemical Engineering Journal, 2024)

Solvent-free mechanochemical synthesis of Mg-gallic acid complex for the fabrication of high-performance supercapacitor porous carbon - Bei Cheng; Beina Yang; Xingyan Xie; Liu Wan; Jian Chen; Cheng Du; Yan Zhang; Mingjiang Xie (Chemical Engineering Journal, 2024)

In situ growth of hydrophobic 3D porous Zn@Ag electrode in achieving excellent performance for eCO2RR - Shenglin Yan; Xinyu Zhang; Samah A. Mahyoub; Bo Zhang; Xiangbei Wan; Yanran Cui; Pengfei Xie; Qiong Wang; Zhenmin Cheng; Zhenglong Li (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Machine learning for high-precision simulation of dissolved organic matter in sewer: Overcoming data restrictions with generative adversarial networks - Feng Hou; Shuai Liu; Wan-Xin Yin; Li-Li Gan; Hong-Tao Pang; Jia-Qiang Lv; Ying Liu; Hong-Cheng Wang (Science of The Total Environment, 2024)

An approach for full space inverse materials design by combining universal machine learning potential, universal property model, and optimization algorithm - Guanjian Cheng; Xin-Gao Gong; Wan-Jian Yin (Science Bulletin, 2024)

Acid-base neutralization strategy for immobilization amino acid ionic liquid within sulfonic acid-based COF as a switch for selective conversion of epoxides - Qingyuan Xue; Linyan Cheng; Qinghua Qu; Lingwei Yang; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

Tuning d-band center of Pt via Pt-Pt5La heterostructure interface as efficient and stable electrocatalyst for oxygen reduction and methanol oxidation reactions in DMFCs - Ziqi Wan; Xinhao Wan; Jianqi Ye; Hao Su; Guanda Cheng; Jie Gao; Wei Gao; Dan Wen (Chemical Engineering Journal, 2024)

Novel fire-resistant SiBCN fiber paper with efficient electromagnetic interference shielding and Joule-heating performance - Qi Ding; Jiahao Yang; Shijia Gu; Chutong Chen; Zhi Cheng; Yongping Liu; Peng Yan; Mingming Si; Sijia Lu; Zongbo Zhang; Lianjun Wang; Yuchi Fan; et al. (Chemical Engineering Journal, 2024)

Fabrication of passive cooling fabric as thermal management curtain for building energy-saving - Chao-Qun Ma; Chao-Hua Xue; Xiao-Jing Guo; Wenzhao Shi; Hui-Di Wang; Meng-Chen Huang; Li Wan; Yong-Gang Wu; Jun Cheng (Chemical Engineering Journal, 2024)

Research on the distribution and influencing factors of fine mode aerosol optical depth (AODf) in China - Haifeng Xu; Jinji Ma; Wenhui Luo; Cheng Wan; Zhengqiang Li (Atmospheric Environment, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Mechanism of HDAC1 Regulating Iron Overload-Induced Neuronal Oxidative Damage After Cerebral Hemorrhage - Jing Han; Jinnan Zhang; Xiaojuan Yao; Meng Meng; Yahui Wan; Yan Cheng (Molecular Neurobiology, 2024)

Provenance of the Southeastern South China Block in the Late Triassic and Initiation of Paleo-Pacific Subduction: Evidence from Detrital Zircon U-Pb Geochronology - Jintao Kong; Zhongjie Xu; Rihui Cheng; Duo Wan (Journal of Earth Science, 2024)

Dual role of dissolved black carbon in sensitized ofloxacin photooxidation: Mechanism and influential factors - Liangyu Li; Bin Wei; Wan Cheng; Yaqi Kang; Xiaoyun Xie; Zhaowei Wang (Science of The Total Environment, 2024)

Formation of filamentous fungal biofilms in water and the transformation of resistance to chlor(am)ine disinfection - Baochun Chang; Qiqi Wan; Gehui Wu; Ya Cheng; Jingyi Wang; Tinglin Huang; Gang Wen (Journal of Hazardous Materials, 2024)

Bensulfuron methyl induced multiple stress responses in the field wheat plants: Microbial community and metabolic network disturbance - Chunran Zhou; Dong Li; Peijuan Miao; Haiyan Cheng; Hui Zhang; Xiaoying Wan; Huan Yu; Yujiao Jia; Qinyong Dong; Canping Pan (Journal of Hazardous Materials, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Laser-induced carbonization strategy for designing efficient dual-layer solar wastewater evaporator - Junfeng Cheng; Xiaoxue Fan; Li Wan; Zhaolan Wang; Siqian Tang; Dun Wu; Dong Wang; Chunlin Liu; Zheng Cao (Chemical Engineering Journal, 2024)

Metformin promotes the survival of random skin flaps via the activation of Nrf2/HO-1 signaling - Yan Chen; Ruxin Cheng; Wenyan Lu; Yonghao Fan; Ye Yu; Ling Huang; Zhenling Wan; Shaojiang Zheng (Chemico-Biological Interactions, 2024)

Phytoremediation as a viable ecological and socioeconomic management strategy - Lai-Yee Phang; Lim Mingyuan; Mitra Mohammadi; Chong-Siang Tee; Mohd Hafis Yuswan; Wan-Hee Cheng; Kok-Song Lai (Environmental Science and Pollution Research, 2024)

How denitrifiers defense ciprofloxacin: Insights from intracellular and extracellular stress response - Hong-Tao Shi; Qin-Yao Zeng; Xiao-Chi Feng; Zi-Jie Xiao; Chen-Yi Jiang; Wen-Qian Wang; Xin Zhang; Hong-Cheng Wang; Wan-Qian Guo; Nan-Qi Ren (Water Research, 2024)

Impacts of landscape dynamics on terrestrial ecosystem health in the Three Gorges Reservoir Area, China - Chunbo Huang; Jing Cheng; Shuangshuang Liu; Yunshan Wan; Jie Zhou; Zelin Liu; Changhui Peng (Journal of Cleaner Production, 2024)

Periodic inundation accelerates the release process of organic carbon from plant litter - Zhonghang Wu; Mao Ye; Ran Li; Jingjie Feng; Hang Wan; Xiaolong Cheng (Journal of Environmental Management, 2024)

Emission and optical characteristics of brown carbon in size-segregated particles from three types of Chinese ships - Fengqin Yang; Fan Zhang; Zeyu Liu; Yingjun Chen; Yan Zhang; Can Wu; Yali Lei; Shijie Liu; Binyu Xiao; Xinyi Wan; Yubao Chen; Yong Han; et al. (Journal of Environmental Sciences, 2024)

An insight into trichomes-deficiency and trichomes-rich black teas by comparative metabolomics: The impact of oxidized trichomes on metabolic profiles and infusion color - Piaopiao Long; Shengxiao Su; Mingchun Wen; Xuyang Liu; Zisheng Han; Jia-Ping Ke; Yu Zhou; Mengting Zhu; Yong Cheng; Yundong Shao; Xiaochun Wan; Liang Zhang (Food Research International, 2024)

Cytoplasmic tail of transmembrane dscam controls antibacterial responses by regulating cell proliferation-related genes in hemocytes of Chinese mitten crab (Eriocheir sinensis) - Hong-hao Xia; Le-mei Zhu; Long-teng Shen; Zhi-cheng Wan (Fish & Shellfish Immunology, 2024)

Dual-responsive metal polyphenol network nanosheets for diabetic wound healing - Bin Cheng; Jie Zhou; Xu Wang; Zihan He; Zhengyi Xu; Jian Wang; Junyu Chen; Zhou Zhu; Weifeng Zhao; Qianbing Wan; Xibo Pei (Chemical Engineering Journal, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Polystyrene nanoplastics exacerbate aflatoxin B1-induced hepatic injuries by modulating the gut−liver axis - Kai-Kai Zhang; Jia-Yuan Wan; Yu-Chuan Chen; Chang-Hao Cheng; He-Qi Zhou; De-Kai Zheng; Zhi-Xian Lan; Qiu-Hong You; Jian Sun (Science of The Total Environment, 2024)

Persulfate activation with biochar supported nanoscale zero- valent iron: Engineering application for effective degradation of NCB in soil - Jinzhong Wan; Yang Guo; Zehang Zhang; Rufeng Deng; Xiang Wang; Shaohua Cao; Xiaodong Zhang; Yifei Miao; Jinlin Jiang; Zhen Song; Tao Long; Cheng Sun; et al. (Science of The Total Environment, 2024)

Development of a novel polydopamine-imprinted MOFs targeted for removal of refractory organic pollutants: Synergistic mechanisms of adsorption and degradation - Jianxin Yi; Jinquan Wan; Yan Wang; Yongwen Ma; Zhicheng Yan; Shiyu Zuo; Cheng Zeng; Wenhui Yuan (Journal of Cleaner Production, 2024)

Water-energy-food(WEF) nexus efficiency of dynamic slack-based measure in 31 provinces and regions in China - Yunyun Gao; Ching-Cheng Lu; Wan-Shui Wu (Journal of Cleaner Production, 2024)

Prevalence and characterization of aminoglycoside resistance gene aph(2”)-If-carrying Campylobacter jejuni - Jin Kang; Cheng Zhang; Shuigen Wan; Wenjun Li; Wenbo Zhao; Longyu Li; Yanhong Shang; Xiang-Dang Du; Dejun Liu; Hong Yao (International Journal of Food Microbiology, 2024)

Transmission mechanism of antibiotic resistance genes and their differences between water and sediment in the Weihe River Basin - Yutong Zhang; Min Wang; Xiaoping Zhou; Wen Cheng; Jiehui Ren; Tian Wan; Xiaoyan Liu (Environmental Research, 2024)

Exploring mycorrhizal diversity in sympatric mycoheterotrophic plants: a comparative study of Monotropastrum humile var. humile and M. humile var. glaberrimum - Ren-Cheng Liu; Wan-Rou Lin; Pi-Han Wang (Mycorrhiza, 2024)

Evaluation of Thermal and Mechanical Properties of Foamed Phosphogypsum-Based Cementitious Materials for Well Cementing in Hydrate Reservoirs - Jiadi Tang; Yusheng Zhao; Wan Cheng; Tianle Liu; Guokun Yang; Mingsheng Chen; Gang Lei; Jian Xu; Yongning Huang (Journal of Marine Science and Engineering, 2024)
As detrimental byproduct waste generated during the production of fertilizers, phosphogypsum can be harmlessly treated by producing phosphogypsum-based cementitious materials (PGCs) for offshore well cementing in hydrate reservoirs. To be specific, the excellent mechanical properties of PGCs significantly promote wellbore stability. And the preeminent temperature control performance of PGCs helps to control undesirable gas channeling, increasing the formation stability of natural gas hydrate (NGH) reservoirs. Notably, to further enhance temperature control performance, foaming agents are added to PGCs to increase porosity, which however reduces the compressive strength and increases the risk of wellbore instability. Therefore, the synergetic effect between temperature control performance and mechanical properties should be quantitatively evaluated to enhance the overall performance of foamed PGCs for well cementing in NGH reservoirs. But so far, most existing studies of foamed PGCs are limited to experimental work and ignore the synergetic effect. Motivated by this, we combine experimental work with theoretical work to investigate the correlations between the porosity, temperature control performance, and mechanical properties of foamed PGCs. Specifically, the thermal conductivity and compressive strength of foamed PGCs are accurately determined through experimental measurements, then theoretical models are proposed to make up for the non-repeatability of experiments. The results show that, when the porosity increases from 6% to 70%, the 7 d and 28 d compressive strengths of foamed PGCs respectively decrease from 21.3 MPa to 0.9 MPa and from 23.5 MPa to 1.0 MPa, and the thermal conductivity decreases from 0.33 W·m−1·K−1 to 0.12 W·m−1·K−1. Additionally, an overall performance index evaluation system is established, advancing the application of foamed PGCs for well cementing in NGH reservoirs and promoting the recycling of phosphogypsum.

Emerging paradigms in sustainable shellfish aquaculture: Microalgae and biofloc technologies for wastewater treatment - Wan Adibah Wan Mahari; Khor Waiho; Hanafiah Fazhan; Elfina Azwar; Alexander Chong Shu-Chien; Mursal Abdulkadir Hersi; Nor Azman Kasan; Say Swan Foo; Kum Yih Wong; Ahmad Shuhaimi Draman; Nyuk Ling Ma; Jo-Shu Chang; et al. (Aquaculture, 2024)

Optimizing grazing exclusion duration for carbon sequestration in grasslands: Incorporating temporal heterogeneity of aboveground biomass and soil organic carbon - Lingfan Wan; Guohua Liu; Jian Sun; Jiaxin Ma; Hao Cheng; Yu Shen; Chenjun Du; Xukun Su (Science of The Total Environment, 2024)

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

By the force of decay: A green strategy to fabricate white rot fungal degraded wood for sustainable oil/water separation - Yang Yang; Jiahui Dai; Ruifeng Cheng; Haiqiu Jiang; Hui Wan; Qiang Gao; Long Yang; Guanben Du; Wei Gao (Journal of Environmental Chemical Engineering, 2024)

Chancelloriids from the Cambrian (Stage 4) Balang Lagerstätte of South China and a reappraisal of their diversification in South China - Hui Zhang; Qiu-Jun Wang; Cheng-Wan Zhang; Die-Die Luo; Xiu-Chun Luo; Yi-Fan Wang; De-Zhi Wang; Xing-Lian Yang (Geobios, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

Humidity-resistant, breathable, waterproof, and bionic triboelectric electronic skins for self-powered haptic sensing and human motion recognition - Xia Liu; Yulong Wang; Wei Wang; Meifei Cheng; Aifang Yu; Lingyu Wan; Junyi Zhai (Chemical Engineering Journal, 2024)

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)

Environmental Flow Increases The Riparian Vegetation Diversity And Community Similarity - Min Guo; Wan-Lai Xue; Chen Wang; Wen-Zhong Li; He Gao; Neil Saintilan; Cheng-Lin Li; Geng Huang; Yu-Yu Wang (Wetlands, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Microbial nanotechnology for agriculture, food, and environmental sustainability: Current status and future perspective - Divjot Kour; Sofia Sharief Khan; Shilpa Kumari; Shaveta Singh; Rabiya Tabbassum Khan; Chandresh Kumari; Swati Kumari; Hemant Dasila; Harpreet Kour; Manpreet Kaur; Seema Ramniwas; Sanjeev Kumar; et al. (Folia Microbiologica, 2024)

Comprehensive indicators optimization construction and lithology measurement while drilling based on drilling parameters - Sun Xin; Cheng Jingyi; Wan Zhijun; Liu Kechen; Yan Wanzi; Xue Minti; Xing Keke (Bulletin of Engineering Geology and the Environment, 2024)

Branched-chain amino acids in ruminant nutrition: Function effects and summary of recent advances - Jishan An; Huitian He; Xinyi Lan; Lei Liu; Zuo Wang; Yu Ge; Weijun Shen; Anwei Cheng; Fachun Wan (Animal Feed Science and Technology, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Remediation of cadmium-contaminated soil using modified activated carbon fiber combined with electrodynamic remediation technology - Dao-lin Zhou; Yue Cheng; Yu-shan Wan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Enhanced interfacial effect via acid theory with boosted photocatalytic performance of nitenpyram removal - Ran Chen; Bo Xu; Heping Cheng; Qianqian Fang; Minghai Ma; Liping Qian; Shunli Wan; Shengyou Xu; Yan Li; Lei Zhang; Shikai Xiang (Chemosphere, 2024)

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Di-n-butyl phthalate induces toxicity in male fetal mouse testicular development by regulating the MAPK signaling pathway - Xinwei Wan; Xudong Cui; Xiang Wang; Mingyang Feng; Shinan Wei; Jia Yu; Sha Cheng; Heng Luo; Jianxin Hu (Toxicology and Applied Pharmacology, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Activation of peroxymonosulfate with natural pyrite-biochar composite for sulfamethoxazole degradation in soil: Organic matter effects and free radical conversion - Ranran Zhao; Tianyu Wang; Zhaowei Wang; Wan Cheng; Liangyu Li; Yaodong Wang; Xiaoyun Xie (Journal of Hazardous Materials, 2024)

Revealing the variances in color formation and bioactivities of seven catechin monomers throughout the enzymatic reaction by colorimetric and mass spectrometry - Wei Hu; Mingchun Wen; Zisheng Han; Xue-Ling Gao; Jia-Ping Ke; Mengting Zhu; Xinlin Wei; Yong Cheng; Xiaochun Wan; Yundong Shao; Liang Zhang (Food Research International, 2024)

Emergence of blaNDM-5–bearing IncHI2/ST2 and p0111 multidrug-resistance plasmids and widespread distribution of IncHI2/ST3–blaNDM-5 plasmids across foods, animals, and humans - Lu-Chao Lv; Cheng-Zhen Wang; Jing-Jing Yu; Yan-Xiang Jiao; Li-Min Deng; Wan-Yun He; Guo-Long Gao; Xiao-Yu Zhang; Li-Tao Lu; Xun Gao; Yi-Yun Liu; Jian-Hua Liu (Food Control, 2024)

Study on non-isothermal reaction and sintering kinetics of Ca(OH)2 particle cluster dehydration with temperature distribution modification - Yishi Gu; Yuxiang Cheng; Zhongjie Shen; Feng Lv; Dayang Wan; Yongchuan Gao; Yuezhang Duan; Jianliang Xu; Qinfeng Liang; Xiaolei Guo; Haifeng Liu (Chemical Engineering Journal, 2024)

Growth, nutrient removal, and lipid productivity promotion of Chlorella sorokiniana by phosphate solubilizing bacteria Bacillus megatherium in swine wastewater: Performances and mechanisms - Ya-Ming Ge; Wan-Chuan Xing; Xiu Lu; Shao-Rou Hu; Jun-Zhi Liu; Wei-Feng Xu; Hai-Xiang Cheng; Feng Gao; Qing-Guo Chen (Bioresource Technology, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Lactate ameliorates palmitate-induced impairment of differentiative capacity in C2C12 cells through the activation of voltage-gated calcium channels - Juan Wan; Chunfang Cheng; Xiaonuo Li; Yuanjie Zhu; Hu Su; Yanchun Gong; Kaizhi Ding; Xiaofei Gao; Caixia Dang; Guoyin Li; Wei Jiang; Li-Hua Yao (Journal of Physiology and Biochemistry, 2024)

Research on the Influencing Factors of AUV Hovering Control in Null-Speed State - Jianguo Wang; Chunmeng Jiang; Lei Wan; Yimei Zhou; Gangyi Hu; Xide Cheng; Gongxing Wu (Journal of Marine Science and Engineering, 2024)
Intelligent underwater vehicles hover by way of a hovering control system. To provide design inputs and maneuver guidance, this study focused on the characteristics of intelligent underwater vehicles during hovering control with the propulsion system shut down, established a mathematical model of hovering control and determined injection and drainage functions based on optimal control theory. From analysis simulation experiments, the influence laws of control parameters, control timing and rate of injection and drainage control upon hovering control were deduced. It is proposed that, at the time of control parameter selection, the continuous injection and drainage rate at each time should be reduced as far as possible to relieve the demand on the volume of the reservoir when the requirement of depth control accuracy has been satisfied. In addition, the injection and drainage control should initiate when depth changes exceed 0.5 m. Suggestions are included on the minimum injection and drainage rate required for different initial disturbances. The proposed suggestions guide the design of hovering control systems and hovering control over intelligent underwater vehicles.

A dynamic modeling approach to predict water inflow during tunnel excavation in relatively uniform rock masses - Zhongxia Li; Jing Xiao; Junwei Wan; Jianmei Cheng; Haibo Feng; Hongbin Zhan; Shuai Yuan; Kun Huang (Tunnelling and Underground Space Technology, 2024)

Lactate induces C2C12 myoblasts differentiation by mediating ROS/p38 MAPK signalling pathway - Chunfang Cheng; Wenxi Li; Yuanqian Ye; Yuanjie Zhu; Mengyuan Tang; Zhihong Hu; Hu Su; Caixia Dang; Juan Wan; Zhibin Liu; Yanchun Gong; Li-Hua Yao (Tissue and Cell, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Synchronous activation for boosting CO2 cycloaddition over the DABCO-derived ionic liquid confined in MIL-101(Cr) nanocages - Yujie Tao; Peiru Wang; Nengjie Feng; Linyan Cheng; Chong Chen; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Cross-talk between Vimentin and autophagy regulates blood-testis barrier disruption induced by cadmium - Na Chen; Xiaoyan Wan; Mei Wang; Yamin Li; Xiaofei Wang; Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Shun Cheng; Yi Shen (Environmental Pollution, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Light-emitting diodes (LEDs) for culturing microalgae and cyanobacteria - Wan Adibah Wan Mahari; Wan Aizuddin Wan Razali; Khor Waiho; Kum Yih Wong; Say Swan Foo; Amyra Suryatie Kamaruzzan; Chan Juinn Chieh Derek; Nyuk Ling Ma; Jo-Shu Chang; Cheng-Di Dong; Yusuf Chisti; Su Shiung Lam (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Photo-Reactivity of dissolved black carbon unveiled by combination of optical spectroscopy and FT-ICR MS analysis: Effects of pyrolysis temperature - Liangyu Li; Wan Cheng; Xiaoyun Xie; Ranran Zhao; Yaodong Wang; Zhaowei Wang (Water Research, 2024)

Enhancing urban climate resilience: A holistic evaluation of urban forest disservices in the aftermath of typhoons - Wan-Yu Liu; Chen-Rui Liu; Chun-Cheng Lin (Urban Climate, 2024)

Polystyrene nanoplastics inhibit beige fat function and exacerbate metabolic disorder in high-fat diet-fed mice - Lina Zhang; Baocheng Wan; Jiangfei Zheng; Liwei Chen; Ye Xuan; Rong Zhang; Zhuo Chen; Cheng Hu; Yi Zhang; Chonghuai Yan (Science of The Total Environment, 2024)

Effects of biochar application methods on greenhouse gas emission and nitrogen use efficiency in paddy fields - Yanze Zhao; Hongfang Jiang; Jiping Gao; Xue Wan; Bingchun Yan; Ya Liu; Guoqing Cheng; Liqiang Chen; Wenzhong Zhang (Science of The Total Environment, 2024)

Hydrodynamic characteristics of frustum-type depressor for sampling midwater trawl - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Yucheng Wang; Shaojian Guo; Hao Yan; Cheng Zhou (Ocean Engineering, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

EtOH-LN cryoembedding workflow to minimize freezing artifact in frozen tissues: A pilot study in preparing tissues compatible with mass spectrometry-based spatial proteomics application - Yong Chiang Tan; Muaatamarulain Mustangin; Nurwahyuna Rosli; Wan Syahira Ellani Wan Ahmad Kammal; Nurismah Md Isa; Teck Yew Low; Pey Yee Lee; Dinesh Kumar Chellappan; Razman Jarmin; Zamri Zuhdi; Azlanudin Azman; Chik Ian; et al. (Cryobiology, 2024)

A radar image seabird identification method for analyzing the effects of FADs on seabirds - Qinglian Hou; Rong Wan; Cheng Zhou (Fisheries Science, 2024)

Therapeutic potential of dietary flavonoid hyperoside against non-communicable diseases: targeting underlying properties of diseases - Jia Xia; Yan Wan; Jiao-jiao Wu; Yu Yang; Jin-Feng Xu; Li Zhang; Dong Liu; Lu Chen; Fei Tang; Hui Ao; Cheng Peng (Critical Reviews in Food Science and Nutrition, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

Enhancing output performance of galloping-based energy harvesting using asymmetric bluff body - Yue Zhang; Guanggui Cheng; Jongwon Seok; Jianning Ding; Wan Sun (Ocean Engineering, 2024)

Numerical simulation-based hydrodynamic interaction of bottom-set gillnet with current and ecological implications - Shaojian Guo; Cheng Zhou; Rong Wan; Jie Cao; Yucheng Wang (Ocean Engineering, 2024)

Insights into the spatial effects of carbon source type on oxygen mass transfer mechanism and microbial community characteristics - Jiehui Ren; Yao Pei; Jiayao Hui; Wen Cheng; Min Wang; Tian Wan (Journal of Water Process Engineering, 2024)

Further understanding NaClO cleaning of bacteria-fouled ultrafiltration membrane: Variation of membrane structure and formation of halogenated by-products - Yujie Cheng; Yujia Zou; Shiwen Yu; Jiaqi Ding; Ying Wan; Lisan Cao; Jingwen Wang; Zongping Wang; Siyang Yue; Pengchao Xie (Journal of Environmental Chemical Engineering, 2024)

Experimental research on the effect of water velocity on phosphorus release from sediments of a plateau cold water type river - Hang Wan; Yanan Huang; Xiaolong Cheng; Jingjie Feng; Ran Li (Journal of Contaminant Hydrology, 2024)

Identification of α-mangostin as a potent inhibitor of β-lactamase OXA-48 - Wenhui Cheng; Yuejuan Zhang; Cheng Chen; Lei Gao; Yuwei Lv; Dian Yu; Bin Chen; Yi Wan (Medicinal Chemistry Research, 2024)

Co-processing plastics waste and biomass by pyrolysis–gasification: a review - Peter Nai Yuh Yek; Yi Herng Chan; Shin Ying Foong; Wan Adibah Wan Mahari; Xiangmeng Chen; Rock Keey Liew; Nyuk Ling Ma; Yiu Fai Tsang; Christian Sonne; Yoke Wang Cheng; Yie Hua Tan; Su Shiung Lam (Environmental Chemistry Letters, 2024)

Signaling pathways involved in microbial indoor air pollutant 3-methyl-1-butanol in the induction of stomatal closure in Arabidopsis - Tu-Trinh Thi Truong; Chi-Chou Chiu; Pei-Yu Su; Jing-Yu Chen; Tri-Phuong Nguyen; Masaru Ohme-Takagi; Ruey-Hua Lee; Wan-Hsing Cheng; Hao-Jen Huang (Environmental Science and Pollution Research, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Vertical biome shifts and climate changes since the last glacial maximum in the southeastern margin of the Tibetan plateau, Southwest China - Xiao Zhang; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Qiuchi Wan; Cong Chen; Yongjie Tang; Yuanfu Yue; Xin Jia; Zhuo Zheng (Quaternary Science Reviews, 2024)

Associations of Serum Iron Status with MAFLD and Liver Fibrosis in the USA: a Nationwide Cross-Section Study - Genfeng Yu; Lan Liu; Tao Qin; Yaosheng Luo; Cheng Song; Xingying Chen; Hualin Duan; Yuqi Jiang; Huixian Zeng; Heng Wan; Jie Shen (Biological Trace Element Research, 2024)

Unraveling the single-atom Fe–N4 catalytic site selectivity generate singlet oxygen via activation of persulfate: Polarizing electric fields changes the electron transfer pathway - Yan Wang; Shiyu Zuo; Cheng Zeng; Jinquan Wan; Zhicheng Yan; Jianxin Yi (Chemosphere, 2023)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Applying artificial intelligence to optimize the trawling path and operational parameters for Antarctic krill - Zhiqiang Liu; Cheng Zhou; Rong Wan; Liuxiong Xu (Ocean Engineering, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

High fire safety thermal protective composite aerogel with efficient thermal insulation and reversible fire warning performance for firefighting clothing - Zhicai Yu; Yuhang Wan; Yi Qin; Qing jiang; Jin-Ping Guan; Xian-Wei Cheng; Xiaochun Wang; Shengnan Ouyang; Xueru Qu; Zhenyu Zhu; Jinfeng Wang; Hualing He (Chemical Engineering Journal, 2023)

Constructing triple-network cellulose nanofiber hydrogels with excellent strength, toughness and conductivity for real-time monitoring of human movements - Jianming Wu; Qian Ma; Qingkai Pang; Shuaishuai Hu; Zhihao Wan; Xiangfang Peng; Xi Cheng; Lihong Geng (Carbohydrate Polymers, 2023)

Effects of water environmental factors and antibiotics on bacterial community in urban landscape lakes - Yutong Zhang; Min Wang; Wen Cheng; Chen Huang; Jiehui Ren; Tian Wan; Kangyi Gao (Aquatic Toxicology, 2023)

Correction to: Exogenous methyl jasmonate (MeJA) enhances the tolerance to cadmium (Cd) stress of okra (Abelmoschus esculentus L.) plants - Feibing Wang; Chenzhong Wan; Wenya Wu; Yuanxin Pan; Xiaomeng Cheng; Chun Li; Jiali Pi; Xinhong Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exogenous methyl jasmonate (MeJA) enhances the tolerance to cadmium (Cd) stress of okra (Abelmoschus esculentus L.) plants - Feibing Wang; Chenzhong Wan; Wenya Wu; Yuanxin Pan; Xiaomeng Cheng; Chun Li; Jiali Pi; Xinhong Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Global warming changes biomass and C:N:P stoichiometry of different components in terrestrial ecosystems - Lingfan Wan; Guohua Liu; Hao Cheng; Shishuai Yang; Yu Shen; Xukun Su (Global Change Biology, 2023)
Global warming has significantly affected terrestrial ecosystems. Biomass and C:N:P stoichiometry of plants and soil is crucial for enhancing plant productivity, improving human nutrition, and regulating biogeochemical cycles. However, the effect of warming on the biomass and C:N:P stoichiometry of different components (plant, leaf, stem, root, litter, soil, and microbial biomass) in various terrestrial ecosystems remains uncertain. We conducted a comprehensive meta‐analysis to investigate the global patterns of biomass and C:N:P stoichiometry responses to warming, as well as interaction relationships based on 1399 paired observations from 105 warming studies. Results indicated that warming had a significant impact on various aspects of plant growth, including an increase in plant biomass (+16.55%), plant C:N ratio (+4.15%), leaf biomass (+16.78%), stem biomass (+23.65%), root biomass (+22.00%), litter C:N ratio (+9.54%) and soil C:N ratio (+5.64%). However, it also decreased stem C:P ratio (−23.34%), root C:P ratio (−12.88%), soil N:P ratio (−14.43%) and soil C:P ratio (−16.33%). The magnitude of warming was the primary drivers of changes of biomass and C:N:P stoichiometry. By establishing the general response curves of changes in biomass and C:N:P ratios with increasing temperature, we demonstrated that warming effect on plant, root, and litter biomass shifted from negative to positive, whereas that on leaf and stem biomass changed from positive to negative as temperature increased. Additionally, the effect of warming on root C:N ratio, root biomass, and microbial biomass N:P ratios shifted from positive to negative, whereas the effects on plant N:P, leaf N:P, leaf C:P, root N:P ratios, and microbial biomass C:N ratio changed from negative to positive with increasing temperature. Our research can help assess plant productivity and optimize ecosystem stoichiometry precisely in the context of global warming.

Promoting short-chain fatty acids production from sewage sludge via acidogenic fermentation: Optimized operation factors and iron-based persulfate activation system - Faxin Liu; Wen Cheng; Jianping Xu; Min Wang; Tian Wan; Jiehui Ren; Dong Li; Qiqi Xie (Chemosphere, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

A comparative transcriptome analysis of how shrimp endure and adapt to long-term symbiosis with Enterocytozoon hepatopenaei infection - Leiting Zhang; Sheng Zhang; Yi Qiao; Xiaowei Cao; Ge Jiang; Jie Cheng; Xihe Wan; Qingguo Meng; Hui Shen (Fish & Shellfish Immunology, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Janus membranes with simultaneous flux enhancement and fouling/wetting resistance prepared by a modified interfacial polymerization process for membrane distillation - Cheng Lei; Jinlong Han; Tengyu Cui; Weifeng Cao; Yinhua Wan; Haoli Zhou; Fei Shen (Desalination, 2023)

Influence of synoptic weather on aerosol variability over East Asia: Present and future - Yi-Chun Chen; Wan-Ling Tseng; Chien-Ming Wu; Wei-Ting Chen; Cheng-Hsiang Chang; Hung-Ying Tseng (Atmospheric Research, 2023)

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Numerical simulation of cooling performance of radiant ceiling system interacting with a ceiling fan - Xingguo Guo; Shuangshuang Wan; Wenhua Chen; Hui Zhang; Edward Arens; Yuanda Cheng; Wilmer Pasut (Energy and Buildings, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Increasing the organic loading rate of household food waste anaerobic digestion by landfill leachate addition: Performance and mechanism - Lianpei Zou; Yi Wang; Ruixin Wu; Shenghao Ji; Yulan Wan; Hui Cheng; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Biochar enhances multifunctionality by increasing the uniformity of energy flow through a soil nematode food web - Baijing Zhu; Bingbing Wan; Ting Liu; Chongzhe Zhang; Liuzhu Cheng; Yanhong Cheng; Shanyi Tian; Xiaoyun Chen; Feng Hu; Joann K. Whalen; Manqiang Liu (Soil Biology and Biochemistry, 2023)

Resource curse and green growth in China: Role of energy transitions under COP26 declarations - Siming Yu; Kang Wan; Cheng Cai; Lingli Xu; Tuanjie Zhao (Resources Policy, 2023)

The intrinsic effects of using rhenium gaskets in hydrothermal diamond anvil cell experiments on background fluorescence, contamination, and redox control - Nanfei Cheng; I-Ming Chou; Ye Wan; Ruoheng Wang; Haiyan Zhang; Ying Chen (Chemical Geology, 2023)

Correction: Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2023)

Assessing Carbon Abatement Costs Considering Forest Carbon Sequestration and Carbon Offset Mechanism: Evidence from Taiwan - Wan-Yu Liu; Yi-Hsin Lu; Chun-Cheng Lin (Forest Science, 2023)
Based on the Greenhouse Gas Reduction and Management Act passed in 2015 and the carbon neutral target in 2050, Taiwan will most likely follow international trends by imposing carbon taxes and establishing carbon offset markets. The positive and negative effects of carbon taxes and carbon offset markets on the economy and the environment merit further investigation. Accordingly, this study adopted a carbon emission reduction (CER) cost prediction model to assess the carbon abatement costs under three scenarios: (1) a carbon offset market exists, and forest carbon sequestration can be used as carbon offsets; (2) a carbon offset market exists, but forest carbon sequestration cannot be used as carbon offsets; and (3) a carbon offset market does not exist. Forests in Taipei (with low carbon emissions) and Kaohsiung (with high carbon emissions) were selected as research sites to explore the benefits of carbon emissions trading and forest carbon sequestration. The results show that CER costs are the lowest in scenario 1 and are the highest in scenario 3. The CER costs of Kaohsiung are higher than those of Taipei. The higher the carbon price, the greater the difference in CER costs between the two cities. Study Implications: The objective of this study was to identify the optimal policy for Taiwan to effectively slow climate change. This study showed that the opening of carbon offset markets and the use of forest carbon sequestration as carbon offsets may prompt regions to increase their forest stock to lower their emission reduction costs. However, achieving 2050 carbon neutral target by solely using forest carbon sequestration is not sufficient in Taiwan.

Influence of surface roughness on the development of moss-dominated biocrusts on mountainous rock-cut slopes in West Sichuan, China - Xin-yue Zhao; Mao-qiang Zhao; Pan-pan Wang; Yu-quan Dai; Wan-qiu Pu; Cheng-min Huang (Journal of Mountain Science, 2023)

Livelihood vulnerability assessment of land-lost farmers in the context of tourism and the COVID-19 pandemic - Wenyue Tang; Qianguang Wang; Hao Cheng; Taohong Liu; Jianmin Wan (Environment, Development and Sustainability, 2023)

Robust self-cleaning membrane with superhydrophilicity and underwater superoleophobicity for oil-in-water separation - Reng-Yu Yue; Peng-Cheng Yuan; Chun-Miao Zhang; Zhang-Hong Wan; Shu-Guang Wang; Xuefei Sun (Chemosphere, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Ultrasound coupled with weak alkali cycling-induced exchange of free sulfhydryl-disulfide bond for remodeling interfacial flexibility of flaxseed protein isolates - Jing Yang; Yuqing Duan; Haihui Zhang; Fenghong Huang; Chuyun Wan; Chen Cheng; Lei Wang; Dengfeng Peng; Qianchun Deng (Food Hydrocolloids, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

Hydroxylamine facilitated catalytic degradation of methylene blue in a Fenton-like system for heat-treatment modified drinking water treatment residues - Yu Zhong; Xiancheng Wan; Xiaoyan Lian; Wenyu Cheng; Xiaoying Ma; Dongtian Wang (Environmental Science and Pollution Research, 2023)

Upcycling medical plastic waste into activated carbons toward environmental safety and sustainability - Junyao Wang; Shuangjun Li; Shuai Deng; Zhanjun Cheng; Xun Hu; Wan Adibah Wan Mahari; Su Shiung Lam; Xiangzhou Yuan (Current Opinion in Environmental Science & Health, 2023)

Dialdehyde xanthan gum and curcumin synergistically crosslinked bioprosthetic valve leaflets with anti-thrombotic, anti-inflammatory and anti-calcification properties - Mengyue Hu; Xu Peng; Shubin Shi; Chang Wan; Can Cheng; Xixun Yu (Carbohydrate Polymers, 2023)

Sodium alginate reinforced polyacrylamide/xanthan gum double network ionic hydrogels for stress sensing and self-powered wearable device applications - Tuo Li; Huige Wei; Yingying Zhang; Tong Wan; Dapeng Cui; Shixiang Zhao; Teng Zhang; Yanxiu Ji; Hassan Algadi; Zhanhu Guo; Liqiang Chu; Bowen Cheng (Carbohydrate Polymers, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Predicting survival after radiosurgery in patients with lung cancer brain metastases using deep learning of radiomics and EGFR status - Chien-Yi Liao; Cheng-Chia Lee; Huai-Che Yang; Ching-Jen Chen; Wen-Yuh Chung; Hsiu-Mei Wu; Wan-Yuo Guo; Ren-Shyan Liu; Chia-Feng Lu (Physical and Engineering Sciences in Medicine, 2023)

Celastrol-loaded biomimetic nanodrug ameliorates APAP-induced liver injury through modulating macrophage polarization - Jing Zheng; Ni Yang; Yingying Wan; Wenjing Cheng; Gan Zhang; Shi Yu; Baoye Yang; Xinyu Liu; Xingyan Chen; Xueliang Ding; Ling Wu; Xiang Yu (Journal of Molecular Medicine, 2023)

SIRT4 in ageing - Ling He; Qingcheng Liu; Jielong Cheng; Mei Cao; Shuaimei Zhang; Xiaolin Wan; Jian Li; Huaijun Tu (Biogerontology, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Holocene warming and evergreen/deciduous forest replacement across eastern China - Zhuo Zheng; Cong Chen; Kangyou Huang; Xiao Zhang; Peter Kershaw; Jun Cheng; Jie Li; Yuanfu Yue; Qiuchi Wan; Yaze Zhang; Yongjie Tang; Mengyuan Wang; et al. (Quaternary Science Reviews, 2023)

Provenance and transport mechanism of gravity core sediments in the deep-water area of the Qiongdongnan Basin, northern South China Sea - Qiang-tai Huang; Yuan-jun Hua; Cheng-lei Zhang; Peng Cheng; Zhi-feng Wan; Tao Hong; Jian-gong Wei (Marine Geology, 2023)

Long-acting removal of high-toxic p-nitrophenol in wastewater via peroxymonosulfate activation by cyclic membrane catalysis - Jingxin Yang; Yongshi Huang; Yuhang Cheng; Xueyan Wu; Jiangyan Lu; Qingnan Wan; Jianxian Feng; Qingyi Zeng; Shuaifei Zhao; Li Yu; Zhu Xiong (Journal of Cleaner Production, 2023)

Biomass degradation: Challenges and strategies in extraction and fractionation of hemicellulose - Nur Izyan Wan Azelee; Hilman Ibnu Mahdi; Yu-Shen Cheng; Norhafiza Nordin; Rosli Md Illias; Roshanida A. Rahman; Shalyda Md Shaarani; Pankaj Bhatt; Sudesh Yadav; Soon Woong Chang; Balasubramani Ravindran; Veeramuthu Ashokkumar (Fuel, 2023)

Structural changes mechanism of lignite during drying: Correlation between macroscopic and microscopic - Cheng Cheng; Mingqiang Gao; Zhenyong Miao; Keji Wan; Qiongqiong He (Fuel, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

A dispersive solid-phase extraction method for the determination of Aristolochic acids in Houttuynia cordata based on MIL-101(Fe): An analytes-oriented adsorbent selection design - Rui Cheng; Xuejin Mao; Jiaying Yu; Fan Liu; Lan Guo; Dongmei Luo; Yiqun Wan (Food Chemistry, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

A comprehensive review on nanocatalysts and nanobiocatalysts for biodiesel production in Indonesia, Malaysia, Brazil and USA - Hilman Ibnu Mahdi; Nurfadhila Nasya Ramlee; José Leandro da Silva Duarte; Yu-Shen Cheng; Rangabhashiyam Selvasembian; Faisal Amir; Leonardo Hadlich de Oliveira; Nur Izyan Wan Azelee; Lucas Meili; Gayathri Rangasamy (Chemosphere, 2023)

Strong linkage between nutrient-cycling functional gene diversity and ecosystem multifunctionality during winter composting with pig manure and fallen leaves - Yarui Cheng; Wenjie Wan (Science of The Total Environment, 2023)

Global meta-analysis reveals differential effects of microplastics on soil ecosystem - Lingfan Wan; Hao Cheng; Yuqing Liu; Yu Shen; Guohua Liu; Xukun Su (Science of The Total Environment, 2023)

Quantification of Asian monsoon variability from 68 ka BP through pollen-based climate reconstruction - Xiao Zhang; Zhuo Zheng; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Yan Zhao; Chen Liang; Xiaoqiang Yang; Qiuchi Wan; Yongjie Tang; Cong Chen; Jie Li (Science Bulletin, 2023)

The Pathology of Primary Familial Brain Calcification: Implications for Treatment - Xuan Xu; Hao Sun; Junyu Luo; Xuewen Cheng; Wenqi Lv; Wei Luo; Wan-Jin Chen; Zhi-Qi Xiong; Jing-Yu Liu (Neuroscience Bulletin, 2023)
Primary familial brain calcification (PFBC) is an inherited neurodegenerative disorder mainly characterized by progressive calcium deposition bilaterally in the brain, accompanied by various symptoms, such as dystonia, ataxia, parkinsonism, dementia, depression, headaches, and epilepsy. Currently, the etiology of PFBC is largely unknown, and no specific prevention or treatment is available. During the past 10 years, six causative genes ( SLC20A2 , PDGFRB , PDGFB , XPR1 , MYORG , and JAM2 ) have been identified in PFBC. In this review, considering mechanistic studies of these genes at the cellular level and in animals, we summarize the pathogenesis and potential preventive and therapeutic strategies for PFBC patients. Our systematic analysis suggests a classification for PFBC genetic etiology based on several characteristics, provides a summary of the known composition of brain calcification, and identifies some potential therapeutic targets for PFBC.

Paper-based analytical device coupled with Bi-MOF: Electric field amplification and fluorescence sensing of glyphosate - Chao-Qun Wan; Yue-Hong Pang; Qiu-Yu Yang; Cheng-Lin Yang; Xiao-Fang Shen (Analytica Chimica Acta, 2023)

What determines the time lags of sap flux with solar radiation and vapor pressure deficit? - Liuliu Wan; Quan Zhang; Lei Cheng; Yujie Liu; Shujing Qin; Jijun Xu; Yongqiang Wang (Agricultural and Forest Meteorology, 2023)

Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2023)

UV-B regulates seasonal greening of albino leaves by modulating CsHY5-inhibiting chlorophyll biosynthesis in Camellia sinensis cv. Huangkui - Xuyang Liu; Xin Cheng; Jingjie Cao; Wenfeng Zhu; Ying Sun; Ning Lin; Xiaochun Wan; Linlin Liu (Plant Science, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Physics-guided genetic programming for predicting field-monitored suction variation with effects of vegetation and atmosphere - Zhi-Liang Cheng; K.K. Pabodha M. Kannangara; Li-Jun Su; Wan-Huan Zhou; Chen Tian (Engineering Geology, 2023)

Impact of biochar amendment on antibiotic removal and ARGs accumulation in constructed wetlands for low C/N wastewater treatment - Fidelis Odedishemi Ajibade; Wan-Xin Yin; Awoke Guadie; Temitope Fausat Ajibade; Ying Liu; Mathieu Nsenga Kumwimba; Wen-Zong Liu; Jing-Long Han; Hong-Cheng Wang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Soil microbial community is resilient to thinning disturbance - Wan-Rou Lin; Wen-Cheng Chen; Pi-Han Wang (Tropical Ecology, 2023)

Calcium lignosulfonate modulates physiological and biochemical responses to enhance shoot multiplication in Vanilla planifolia Andrews - Kah-Lok Thye; Wan Muhamad Asrul Nizam Wan Abdullah; Janna Ong-Abdullah; Dhilia Udie Lamasudin; Chien-Yeong Wee; Mohd Hafis Yuswan Mohd Yusoff; Jiun-Yan Loh; Wan-Hee Cheng; Kok-Song Lai (Physiology and Molecular Biology of Plants, 2023)

Mitochondrial SIRT3 Deficiency Results in Neuronal Network Hyperexcitability, Accelerates Age-Related Aβ Pathology, and Renders Neurons Vulnerable to Aβ Toxicity - Isabella Perone; Nathaniel Ghena; Jing Wang; Chelsea Mackey; Ruiqian Wan; Sulochan Malla; Myriam Gorospe; Aiwu Cheng; Mark P. Mattson (NeuroMolecular Medicine, 2023)

Abundance and diversity of eukaryotic rather than bacterial community relate closely to the trophic level of urban lakes - Wenjie Wan; Geoffrey Michael Gadd; Donglan He; Wenzhi Liu; Xiang Xiong; Luping Ye; Yarui Cheng; Yuyi Yang (Environmental Microbiology, 2023)
Scientific understanding of biotic effects on the water trophic level is lacking for urban lakes during algal bloom development stage. Based on the Illumina MiSeq sequencing, quantitative polymerase chain reaction (PCR), and multiple statistical analyses, we estimated distribution patterns and ecological roles of planktonic bacteria and eukaryotes in urban lakes during algal bloom development stage (i.e., April, May, and June). Cyanobacteria and Chlorophyta mainly dominated algal blooms. Bacteria exhibited significantly higher absolute abundance and community diversity than eukaryotes, whereas abundance and diversity of eukaryotic rather than bacterial community relate closely to the water trophic level. Multinutrient cycling (MNC) index was significantly correlated with eukaryotic diversity rather than bacterial diversity. Stronger species replacement, broader environmental breadth, and stronger phylogenetic signal were found for eukaryotic community than for bacterial community. In contrast, bacterial community displayed stronger community stability and environmental constraint than eukaryotic community. Stochastic and differentiating processes contributed more to community assemblies of bacteria and eukaryotes. Our results emphasized that a strong linkage between planktonic diversity and MNC ensured a close relationship between planktonic diversity and the water trophic level of urban lakes. Our findings could be useful to guide the formulation and implementation of environmental lake protection measures.

Uptake kinetics and subcellular distribution of three classes of typical pesticides in rice plants - Jianan Liu; Jinjin Cheng; Chunli Zhou; Liya Ma; Xiaolong Chen; Yong Li; Xing Sun; Xiaolong Yan; Renhua Geng; Qun Wan; Xiangyang Yu (Science of The Total Environment, 2023)

Simultaneous stabilization of Pb, Cd, and As in soil by rhamnolipid coated sulfidated nano zero-valent iron: Effects and mechanisms - Huihui Song; Weiyu Liang; Kailun Luo; Gehui Wang; Qiannan Li; Xiaowen Ji; Jiang Wan; Xuechun Shao; Kailin Gong; Wei Zhang; Cheng Peng (Journal of Hazardous Materials, 2023)

Giant Mesozoic gold ores derived from subducted oceanic slab and overlying sediments - Kun-Feng Qiu; Jun Deng; Crystal Laflamme; Zheng-Yu Long; Ruo-Qi Wan; Frederic Moynier; Hao-Cheng Yu; Jing-Yuan Zhang; Zheng-Jiang Ding; Richard Goldfarb (Geochimica et Cosmochimica Acta, 2023)

A parametric investigation of methane jets in direct-injection compression-ignition conditions - Quancen Wan; Guanxiong Zhai; Cheng Wang; Anthony C.Y. Yuen; Paul R. Medwell; Sanghoon Kook; Guan Heng Yeoh; Qing Nian Chan (Fuel, 2023)

Tourists' preference for colors of forest landscapes and its implications for forest landscape planning policies - Wan-Yu Liu; Chen Tsao; Chun-Cheng Lin (Forest Policy and Economics, 2023)

Fusion of spectra and texture data of hyperspectral imaging for prediction of myoglobin content in nitrite-cured mutton - Guoling Wan; Shuxiang Fan; Guishan Liu; Jianguo He; Wei Wang; Yan Li; Lijuan Cheng; Chao Ma; Mei Guo (Food Control, 2023)

Sustained power output from an algal biophotovoltaic (BPV) platform using selected marine and freshwater microalgae - Cheng-Han Thong; Fong-Lee Ng; Vengadesh Periasamy; Wan Jeffrey Basirun; G. Gnana Kumar; Siew-Moi Phang (Journal of Applied Phycology, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

S100A4-dependent glycolysis promotes lymphatic vessel sprouting in tumor - Anqi Li; Linyu Zhu; Ningjing Lei; Jiajia Wan; Xixi Duan; Shuangqing Liu; Yanru Cheng; Ming Wang; Zhuoyu Gu; Huilei Zhang; Yueyue Bai; Li Zhang; et al. (Angiogenesis, 2023)

Corrigendum to: Impacts of farmland application of antibiotic-contaminated manures on the occurrence of antibiotic residues and antibiotic resistance genes in soil: A meta-analysis study [Chemosphere 300 (Aug 2022) 134529] - Yu Zhang; Dengmiao Cheng; Jun Xie; Yuting Zhang; Yu Wan; Yueqiang Zhang; Xiaojun Shi (Chemosphere, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Heavy rare earth element and crustal-derived silicon enrichment in Huayangchuan carbonatites, Qinling orogenic belt - Chun-wan Wei; Cheng Xu; Wen-lei Song; Wei Chen; Aiguo Shi; Zhuoqi Li; Chaoxi Fan (Lithos, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

In vitro toxicity assessment of haloacetamides via a toxicogenomics assay - Dong Li; Wen Cheng; Jiehui Ren; Lu Qin; Xing Zheng; Tian Wan; Min Wang (Environmental Toxicology and Pharmacology, 2023)

Benzotriazole ultraviolet stabilizer UV-234 promotes foam cell formation in RAW264.7 macrophages - Xinming Shen; Wenxin Hu; Chenke Xu; Cheng Xu; Yi Wan; Jianying Hu (Environmental Pollution, 2023)

Axial compressive performance of RC columns strengthened with prestressed CFRP fabric combined with UHPC jacket - Chun-ling Lu; Kang Ouyang; Cheng Guo; Qiang Wang; Hou-qiong Chen; Wan-xu Zhu (Engineering Structures, 2023)

Unexpected F- removal by Co2Al-LDHs: Performance and new insight - Fansong Liu; Lei Wan; Haiying Wang; Cheng Zhong; Xiaobo Min; Liyuan Zhang (Chemical Engineering Journal, 2023)

The disruption of calcium and hydrogen ion homeostasis of submerged macrophyte Vallisneria natans (Lour.) Hara caused by microcystin-LR - Chen Cheng; Alan D. Steinman; Qingju Xue; Xiang Wan; Liqiang Xie (Aquatic Toxicology, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

The transition from Palaeo-Asian to marginal Pacific tectonic domain experienced in the Eastern North China Craton: evidence from Late Jurassic sediment provenance in the North Yellow Sea Basin - Haitian Yu; Zhongjie Xu; Rihui Cheng; Duo Wan; Dan Gao; Zhen Zhang (Earth Science Informatics, 2022)

Trimethylamine N-oxide facilitates the progression of atrial fibrillation in rats with type 2 diabetes by aggravating cardiac inflammation and connexin remodeling - Wan-Ying Jiang; Jun-Yu Huo; Sheng-Chan Wang; Yan-Di Cheng; Yi-Ting Lyu; Zhi-Xin Jiang; Qi-Jun Shan (Journal of Physiology and Biochemistry, 2022)

Elucidation of endothelial progenitor cell dysfunction in diabetes by RNA sequencing and constructing lncRNA–miRNA–mRNA competing endogenous RNA network - Gui Wan; Zhao Xu; Xuejiao Xiang; Maojie Zhang; Tao Jiang; Jing Chen; Shengbo Li; Cheng Wang; Chengqi Yan; Xiaofan Yang; Zhenbing Chen (Journal of Molecular Medicine, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Hsa_circ_0070194 targets the miR-384/HDAC2 axis to enhance proliferation, cell cycle, migration and invasion of trophoblast cells - Huan Chen; Cheng Gao; Wenhui Zhu; Rong Wan; Mei Xiong (Molecular & Cellular Toxicology, 2022)

Recent advances in alleviating food allergenicity through fermentation - Xiaowen Pi; Yili Yang; Yuxue Sun; Qiang Cui; Yin Wan; Guiming Fu; Hongbing Chen; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Food irradiation: a promising technology to produce hypoallergenic food with high quality - Xiaowen Pi; Yili Yang; Yuxue Sun; Xibo Wang; Yin Wan; Guiming Fu; Xin Li; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Association between meteorological factors and hospital admissions for uveitis in Hefei, China: a time-series study - Fan Cao; Yi-Sheng He; Kun Xiang; Cheng-Huan Wan; Wei Liu; Yan-Chao Gui; Hai-Feng Pan; Zheng-Xuan Jiang; Li-Ming Tao (Environmental Science and Pollution Research, 2022)

Comparison of Different Chemical Extraction Methods for Predicting the Bioavailability and Phytotoxicity of Soil PAEs to Green Vegetables (Brassica Rapa Var. Chinensis) - Jinjin Cheng; Xiaolong Chen; Lili Tian; Qun Wan; Xiangyang Yu (Bulletin of Environmental Contamination and Toxicology, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Identification of Distributed Dynamic Characteristics of Journal Bearing with Large Aspect Ratio under Shaft Bending - Wu Ouyang; Qilin Liu; Qichao Cheng; Gao Wan; Yong Jin (Journal of Marine Science and Engineering, 2022)
The classical theory of centralized dynamic characteristics with eight coefficients is adopted for traditional journal bearings. However, under cantilevered load, distributed dynamic characteristics along the axial direction will be generated for the journal bearing with a large aspect ratio (L/D). A double-section loading method simulating shaft bending and excitation was developed, a dynamic characteristic test-rig of a large-aspect-ratio bearing was set-up, the novel four-time vertical excitation method and eight-time cross excitation method were put forward, and the equations of 16 dynamic characteristic coefficients of the bearing were deduced. The dynamic characteristic test was carried out. The results showed that the four-time vertical excitation method had a small response amplitude in the horizontal direction, and was vulnerable to interference by the vibration of the test-rig. The eight-time cross excitation method had a higher SNR with more accurate identification results. When the cantilevered load was not applied, the dynamic characteristic coefficients were evenly distributed along the axial direction, the stiffness coefficients fluctuated slightly as the rotation rate increased, while the main damping coefficients decreased significantly. Shaft bending resulted in a significant increase in local dynamic characteristic coefficients, in which the relative increase in the stiffness coefficients was greater than that of the damping coefficients. Increasing the rotational speed can weaken the effect of shaft bending, and key factors that cause the axially nonuniform distribution of dynamic characteristic coefficients of the bearing are shaft bending and large aspect ratio under low speed and cantilevered load.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Geochemical characteristics of cold-seep carbonates in Shenhu area, South China Sea - Chongmin Chen; Lifeng Zhong; Zhifeng Wan; Chiyu Cheng; Wei Zhou; Xing Xu (Journal of Oceanology and Limnology, 2022)

Regulation of endothelial progenitor cell functions during hyperglycemia: new therapeutic targets in diabetic wound healing - Gui Wan; Yangyang Chen; Jing Chen; Chengqi Yan; Cheng Wang; Wenqing Li; Renqun Mao; Hans-Günther Machens; Xiaofan Yang; Zhenbing Chen (Journal of Molecular Medicine, 2022)

Knockout of GGPPS1 restrains rab37-mediated autophagy in response to ventilator-induced lung injury - Zexu Wang; Meizi Chen; Xia Pan; Li Wang; Cheng Yin; Qiuqi Lin; Jingjing Jiang; Yunlei Zhang; Bing Wan (Human Cell, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Spatiotemporal distribution and the passive dispersal of fungal spores through HVAC systems - Wan-Rou Lin; Yung-Hung Ho; Wai Kwan Lee; Hsuan-Min Cheng; Pi-Han Wang (Aerobiologia, 2022)

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2022)
Purpose Many studies have shown that multiparametric magnetic resonance imaging (MRI) may be helpful for differentiating malignant renal cell carcinomas (RCCs) from benign lesions. However, the key imaging characteristics that differ between malignant and benign tumors still require further discussion. Methods We analyzed 60 adult patients diagnosed with 72 small renal masses (SRMs) who received preoperative MRI from 2014 to 2019 at a hospital in Taiwan. The MRI features included conventional MRI parameters, diffusion-weighted imaging (DWI) data, and dynamic contrast-enhanced (DCE) patterns, which were documented and compared among the four common subtypes: clear cell RCC (ccRCC), papillary RCC (pRCC), angiomyolipoma (AML) and other types of RCC. The apparent diffusion coefficient (ADC) values of high- and low-grade RCCs were also analyzed. Results The results show that ccRCC had higher T2-weighted signal intensity than the other three subgroups, a higher arterial wash-in index (AWI) and ADC value than AML and pRCC, and manifested a plateau ( n = 9, 25%) or washout (n = 27, 75%) enhancement pattern. AMLs exhibited more intravoxel fat than the other three subtype groups, and half of the AMLs (6 in 12) contained bulk fat. pRCC demonstrated a more progressive (n = 3, 60%) enhancement pattern than the other three subgroups. The ADC value of high-grade RCCs was significantly lower than that of low-grade RCCs. Conclusion These findings may indicate that multiparametric MRI is useful in differentiating among four common pathological types of SRMs, and the ADC value may be helpful in evaluating the histological grade of malignancy.

SDF-1 secreted by mesenchymal stem cells promotes the migration of endothelial progenitor cells via CXCR4/PI3K/AKT pathway - Xiaoyi Wang; Huijiao Jiang; Lijiao Guo; Sibo Wang; Wenzhe Cheng; Longfei Wan; Zhongzhou Zhang; Lihang Xing; Qing Zhou; Xiongfeng Yang; Huanhuan Han; Xueling Chen; et al. (Journal of Molecular Histology, 2021)

The r-X1 deletion induces terminal deficiencies in the maize B chromosome - Yen-Hua Huang; Tzu-Che Lin; Wan-Yi Chiou; Ya-Ming Cheng (Chromosome Research, 2021)

Application of Feature Point Matching Technology to Identify Images of Free-Swimming Tuna Schools in a Purse Seine Fishery - Qinglian Hou; Cheng Zhou; Rong Wan; Junbo Zhang; Feng Xue (Journal of Marine Science and Engineering, 2021)
Tuna fish school detection provides information on the fishing decisions of purse seine fleets. Here, we present a recognition system that included fish shoal image acquisition, point extraction, point matching, and data storage. Points are a crucial characteristic for images of free-swimming tuna schools, and point algorithm analysis and point matching were studied for their applications in fish shoal recognition. The feature points were obtained by using one of the best point algorithms (scale invariant feature transform, speeded up robust features, oriented fast and rotated brief). The k-nearest neighbors (KNN) algorithm uses ‘feature similarity’ to predict the values of new points, which means that new data points will be assigned a value based on how closely they match the points that exist in the database. Finally, we tested the model, and the experimental results show that the proposed method can accurately and effectively recognize tuna free-swimming schools.

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

SETD3 Downregulation Mediates PTEN Upregulation-Induced Ischemic Neuronal Death Through Suppression of Actin Polymerization and Mitochondrial Function - Xiangyu Xu; Yu Cui; Congqin Li; Yuyang Wang; Jing Cheng; Songfeng Chen; Jiangdong Sun; Jinyang Ren; Xujin Yao; Jingchen Gao; Xiaohong Huang; Qi Wan; et al. (Molecular Neurobiology, 2021)

Enhanced degradation of reactive brilliant red X-3B by photocatalysis integrated with micro-electrolysis - Gong Cheng; Yibo Zhang; Lei Sun; Jing Wan; Zhang Li; Chenyuan Dang; Jie Fu (Environmental Science and Pollution Research, 2021)

Spatiotemporal characteristics and trend assessment of Ms ≥ 5.6 earthquakes in the Tianshan area of China based on co-occurrence analysis and commensurability - Jia Wan; Jun-Ping Yan; Zi-Qiang Liu; Xiao-Meng Wang; Yu-Feng Zhang; Cheng-Bo Wang (Applied Geophysics, 2021)

Genetic mapping reveals BjRf as a candidate gene controlling fertility restoration of the oxa CMS in Brassica juncea - Qiqi Cheng; Peijie Yao; Hui Li; Yiming Han; Kejing Xu; Shuangping Heng; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2021)

Transcriptome analysis reveals hub genes in the hepatopancreas of Exopalaemon carinicauda in response to hypoxia and reoxygenation - Wenjun Shi; Pan Wang; Runhao Hu; Xihe Wan; Hui Shen; Hui Li; Libao Wang; Yi Qiao; Ge Jiang; Jie Cheng; Zeyu Yang (Aquaculture International, 2021)

Exploring the validity of using immersive virtual reality technique on perceived crowding of recreational environment - Ting-Hsuan Wang; Wan-Hsuan Wu; Li Shen; Chia-Kuen Cheng (Landscape and Ecological Engineering, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

Genome-wide identification and expression analysis of the MADS-box transcription factor family in Camellia sinensis - Zai-Bao Zhang; Yuan-Jin Jin; Hou-Hong Wan; Lin Cheng; Zhi-Guo Feng (Journal of Applied Genetics, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Upper Ocean Temperatures Hit Record High in 2020 - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Ricardo Locarnini; Bin Zhang; Fujiang Yu; Liying Wan; Xingrong Chen; Xiangzhou Song; Yulong Liu; et al. (Advances in Atmospheric Sciences, 2021)

Improving Oral Bioavailability of Luteolin Nanocrystals by Surface Modification of Sodium Dodecyl Sulfate - Jiali Liu; Yongbing Sun; Meng Cheng; Qiaoming Liu; Wan Liu; Chao Gao; Jianfang Feng; Yi Jin; Liangxing Tu (AAPS PharmSciTech, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Spatial variability of bigeye tuna habitat in the Pacific Ocean: Hindcast from a refined ecological niche model - Cheng Zhou; Rong Wan; Jie Cao; Liuxiong Xu; Xuefang Wang; Jiangfeng Zhu (Fisheries Oceanography, 2021)
Habitat distribution is critically informative for stock assessment, since incorporating its variabilities can have important implications for the estimation of stock biomass or the relative abundance index. A refined ecological niche model with habitat characteristic parameterization was developed to reconstitute a 3‐D ecological map of bigeye tuna in the Pacific Ocean. We determined the boundaries and hierarchies of oceanographic features and hydrological conditions at horizontal and vertical scales to define the habitat preference of bigeye tuna associated with their feeding and physiological requirements. Ecogeographic projections underlined the depth‐ and region‐specific habitat distribution of bigeye tuna, with noticeable dynamic variations in the response to climate variability. Depths from 300 to 400 m represented layers of the most productive habitat, which was widespread through the equatorial Pacific Ocean and extended to the north‐central Pacific Ocean. The proportion of high‐quality habitat size in the north Pacific had a strictly regular intra‐annual cycle with peaks during the winter. Climate variability appeared to disturb the balance of the regular fluctuations in habitat size in the equatorial Pacific. Habitat hotspots during an El Niño period were characterized by their expansion to the north of the Hawaiian islands, shrinkage in the west for the hotspot band north of the Equator, and an eastern shift for the band south of the Equator. This variability may be the consequence of the incorporated fluctuations of the oxygen minimum zones (OMZ), current systems, and stratification in the open ocean.

Climate‐induced nonlinearity in pelagic communities and non‐stationary relationships with physical drivers in the Kuroshio ecosystem - Shuyang Ma; Yongjun Tian; Caihong Fu; Haiqing Yu; Jianchao Li; Yang Liu; Jiahua Cheng; Rong Wan; Yoshiro Watanabe (Fish and Fisheries, 2021)
Climate‐induced nonlinearity in biological variability and non‐stationary relationships with physical drivers are crucial to understand responses of marine organisms to climate variability. These phenomena have raised concerns in the northeastern North Pacific, but are out of the spotlight in the northwestern North Pacific in spite of potential implications for this productive system under increased climate variability. Pelagic communities in the Kuroshio ecosystem have both ecological and economic importance. However, patterns of climate‐induced nonlinearity in pelagic communities are not well understood, and existence of non‐stationarity in their relationships with physical drivers remains obscure. Here, we compile large numbers of climatic, oceanic and biological long‐term time‐series data and employ diverse statistical techniques to reveal such climate‐induced nonlinearity and non‐stationarity. Results show that pelagic communities in the Tsushima and Pacific areas (major areas in the Kuroshio ecosystem) had regime shifts in the late 1990s and late 1980s, respectively. Winter sea surface temperatures in the Kuroshio Current path and in the eastern part of East China Sea, which are respectively affected by the Kuroshio Current and Siberian High, correlate with dominant variability patterns in their pelagic communities. Furthermore, non‐stationarity was identified with threshold years in the 1990s in the Tsushima area and in the 1980s in the Pacific area as a possible result of the declined variances in the Siberian High and Aleutian Low, respectively. Our findings provide insights on spatial differentiation of climate‐induced nonlinearity and non‐stationarity, which are valuable for the management of pelagic communities in the northwestern North Pacific under changing climatic conditions.

Sphingosylphosphorylcholine alleviates hypoxia-caused apoptosis in cardiac myofibroblasts via CaM/p38/STAT3 pathway - Ying Li; Qi Qi; Wan-cheng Yang; Tian-liang Zhang; Chen-chen Lu; Yu-juan Yao; Wei-hua Kong; Jing Zhao (Apoptosis, 2020)

Fine-mapping of the BjPur gene for purple leaf color in Brassica juncea - Shuangping Heng; Qiqi Cheng; Tian Zhang; Xujia Liu; Hao Huang; Peijie Yao; Zhixin Liu; Zhengjie Wan; Tingdong Fu (Theoretical and Applied Genetics, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Evaluation and Comparison of the Toxic Effects of MgO NPs, ZnO NPs, α-Fe2O3 NPs, γ-Fe2O3 NPs, and Fe3O4 NPs on the Remediation for Cadmium-Related Effects in Wheat Seedlings - Yongchao Cheng; Yuxuan Cheng; Han Zheng; Yaxin Song; Ruizhe Li; Fengting Wan; Junli Li (Water, Air, & Soil Pollution, 2020)

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Blood and Cerebrospinal Fluid Autoantibody to Aβ Levels in Patients with Alzheimer’s Disease: a Meta-Analysis Study - Xiao-Wan Li; Xi-Xi Li; Qing-Shan Liu; Yong Cheng (Journal of Molecular Neuroscience, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

A new metagenome binning method based on gene uniqueness - Yulin Kang; Cheng Wan; Sifen Lu; Zhehan Fu; Antony K. Chen; Zuhong Lu (Genes & Genomics, 2020)

Tomato grafting onto Torubamu (Solanum melongena): miR166a and miR395b reduce scion Cd accumulation by regulating sulfur transport - Lei He; Hetong Wang; Qiang Zhao; Zhibo Cheng; Peidong Tai; Wan Liu (Plant and Soil, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Modeling of Borehole Hydraulic Fracture Initiation and Propagation with Pre-existing Cracks Using the Displacement Discontinuity Method - Wan Cheng; Chunhua Lu; Zhidong Zhou (Geotechnical and Geological Engineering, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Fabrication of Fine Puerarin Nanocrystals by Box–Behnken Design to Enhance Intestinal Absorption - Meng Cheng; Fangying Yuan; Jiali Liu; Wan Liu; Jianfang Feng; Yi Jin; Liangxing Tu (AAPS PharmSciTech, 2020)

Phosphorus-fertilisation has differential effects on leaf growth and photosynthetic capacity of Arachis hypogaea L. - Qingwen Shi; Jiayin Pang; Jean Wan Hong Yong; Chunming Bai; Caio Guilherme Pereira; Qiaobo Song; Di Wu; Qiping Dong; Xin Cheng; Feng Wang; Junlin Zheng; Yifei Liu; et al. (Plant and Soil, 2020)

Nitrogen transformation mediated by nitrate-dependent iron oxidation in anoxic freshwater - Boyi Cheng; Yumei Hua; Jianwei Zhao; Guanglong Liu; Xiaoqiong Wan (Journal of Soils and Sediments, 2020)

Record-Setting Ocean Warmth Continued in 2019 - Lijing Cheng; John Abraham; Jiang Zhu; Kevin E. Trenberth; John Fasullo; Tim Boyer; Ricardo Locarnini; Bin Zhang; Fujiang Yu; Liying Wan; Xingrong Chen; Xiangzhou Song; et al. (Advances in Atmospheric Sciences, 2020)

Comparison between two kinds of natural pollen traps in tropical China: ants’ nests on tree branches versus surface soil - Zhi-Yong Zhang; Feng-Chun Yang; Dong-Mei Cheng; David K. Ferguson; Wan Hu; Yue-Zhuo Li; Cheng-Sen Li (Palynology, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

In search of alternative proteins: unlocking the potential of underutilized tropical legumes - Acga Cheng; Murthazar Naim Raai; Nurul Amalina Mohd Zain; Festo Massawe; Ajit Singh; Wan Abd Al Qadr Imad Wan-Mohtar (Food Security, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Identifying the Design Alternatives and Flow Interference of Tuna Purse Seine by the Numerical Modelling Approach - Cheng Zhou; Liuxiong Xu; Hao Tang; Fuxiang Hu; Pingguo He; Taisei Kumazawa; Xuefang Wang; Rong Wan; Shuchuang Dong (Journal of Marine Science and Engineering, 2019)
Dynamic responses of tuna purse seine to currents were numerically studied with regard to the vertical subsidence and global load distribution, and determinant attributes were identified. We rebuilt the submerged geometry of a purse seine net using the lumped mass method with hydrodynamic coefficients obtained from measurements of the prototype material, as well as a mesh grouping method, which corrects the twine diameter and netting material density for the equivalent net by introducing the compensation coefficient. Uneven tension distribution showed that it was vulnerable to high loads in the bunt area at shooting and along the lead line at pursing. High loads were present at the convex sections of net circles in the direction of the current. Higher shooting speeds resulted in well-balanced sinking, while a reduced hanging ratio of netting panels was beneficial to faster sinking. While large mesh sizes reduce water resistance and increase sinking velocity, extensive use should be cautioned in terms of the sensibility to stress. Comparing two options of different proportions of large-mesh panels, mesh sizes doubled for 15 strips versus 5 strips, suggesting that the 15 strip option would pose a higher risk of strand vulnerability, while the 5 strip option may be a more balanced alternative with a lower mesh density and a lower mesh stress.

Adsorption Removal of Cr(VI) with Activated Carbon Prepared by Co-pyrolysis of Rice Straw and Sewage Sludge with ZnCl2 Activation - Liangqian Fan; Wenxin Wan; Xianda Wang; Jie Cai; Fenghui Chen; Wei Chen; Lin Ji; Hongbing Luo; Lin Cheng (Water, Air, & Soil Pollution, 2019)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Impact of LDB3 gene polymorphisms on clinical presentation and implantable cardioverter defibrillator (ICD) implantation in Chinese patients with idiopathic dilated cardiomyopathy - Dong-fei Wang; Jia-lan Lyu; Juan Fang; Jian Chen; Wan-wan Chen; Jia-qi Huang; Shu-dong Xia; Jian-mei Jin; Fang-hong Dong; Hong-qiang Cheng; Ying-ke Xu; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2019)

Risk Causal Analysis of Traffic-Intensive Waters Based on Infectious Disease Dynamics - Yong-jun Chen; Qing Liu; Cheng-peng Wan (Journal of Marine Science and Engineering, 2019)
Accidents occur frequently in traffic-intensive waters, which restrict the safe and rapid development of the shipping industry. Due to the suddenness, randomness, and uncertainty of accidents in traffic-intensive waters, the probability of the risk factors causing traffic accidents is usually high. Thus, properly analyzing those key risk factors is of great significance to improve the safety of shipping. Based on the analysis of influencing factors of ship navigational risks in traffic-intensive waters, this paper proposes a cloud model to excavate the factors affecting navigational risk, which could accurately screen out the key risk factors. Furthermore, the risk causal model of ship navigation in traffic-intensive waters is constructed by using the infectious disease dynamics method in order to model the key risk causal transmission process. Moreover, an empirical study of the Yangtze River estuary is conducted to illustrate the feasibility of the proposed models. The research results show that the cloud model is useful in screening the key risk factors, and the constructed causal model of ship navigational risks in traffic-intensive waters is able to provide accurate analysis of the transmission process of key risk factors, which can be used to reduce the navigational risk of ships in traffic-intensive waters. This research provides both theoretical basis and practical reference for regulators in the risk management and control of ships in traffic-intensive waters.

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

WSL6 encoding an Era-type GTP-binding protein is essential for chloroplast development in rice - Yinglun Sun; Yunlu Tian; Shuhan Cheng; Yunlong Wang; Yuanyuan Hao; Jianping Zhu; Xiaopin Zhu; Yuanyan Zhang; Mingzhou Yu; Jie Lei; Xiuhao Bao; Hongming Wu; et al. (Plant Molecular Biology, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Numerical Simulation for the Dynamic Breakout of a Borehole Using Boundary Element Method - Wan Cheng; Guosheng Jiang; Zhidong Zhou; Zijun Wei; Xiaodong Li (Geotechnical and Geological Engineering, 2019)

Seasonal changes in the chemical composition and reactivity of dissolved organic matter at the land-ocean interface of a subtropical river - Liyang Yang; Qiong Cheng; Wan-E Zhuang; Hui Wang; Wei Chen (Environmental Science and Pollution Research, 2019)

Prevalence of mycotoxins in feed and feed ingredients between 2015 and 2017 in Taiwan - Ching-Kuo Yang; Yeong-Hsiang Cheng; Wan-Ting Tsai; Rou-Wan Liao; Chia-Sheng Chang; Wan-Chu Chien; Jia-Cin Jhang; Yu-Hsiang Yu (Environmental Science and Pollution Research, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Identification and Analysis of Vulnerability in Traffic-Intensive Areas of Water Transportation Systems - Yong-jun Chen; Qing Liu; Cheng-peng Wan; Qin Li; Peng-wei Yuan (Journal of Marine Science and Engineering, 2019)
Water transportation accidents have occurred frequently in recent years. In order to improve the emergency response capability of water transportation systems under traffic-intensive conditions, this paper identifies and analyzes the vulnerability in traffic-intensive areas of water transportation systems. Firstly, the vulnerability identification model was constructed based on the analysis of characteristics and the vulnerability-influencing factors of water transportation systems. The newly proposed model is composed of three parts including the DEMATEL (Decision Making Trial and Evaluation Laboratory) method, ISM (interpretative structural modeling) model, and AHP (Analytic Hierarchy Process)–entropy weight method. Finally, a case study of the Yangtze River was conducted to test the logicality and feasibility of the proposed model. The research results reveal that traffic flow density, ship traffic, tides, fog, and bad weather are the key factors affecting the vulnerability of water transportation in traffic-intensive areas of the Yangtze River estuary. However, the influence of navigation aid configuration, berth, anchorage, and obstruction on the system vulnerability is relatively lower. The findings of this study can provide helpful references for maritime administration authorities on the management of water transportation safety.

MiR-15b-5p is Involved in Doxorubicin-Induced Cardiotoxicity via Inhibiting Bmpr1a Signal in H9c2 Cardiomyocyte - Guo-xing Wan; Lan Cheng; Hai-lun Qin; Yun-zhang Zhang; Ling-yu Wang; Yong-gang Zhang (Cardiovascular Toxicology, 2019)

Early heading 7 interacts with DTH8, and regulates flowering time in rice - Maohong Cai; Saihua Chen; Mingming Wu; Tianhui Zheng; Liang Zhou; Chaonan Li; Huan Zhang; Jiachang Wang; Xinyang Xu; Juntao Chai; Yulong Ren; Xiuping Guo; et al. (Plant Cell Reports, 2019)

Long-term seasonal forecasting of a major migrant insect pest: the brown planthopper in the Lower Yangtze River Valley - Gao Hu; Ming-Hong Lu; Don R. Reynolds; Hai-Kou Wang; Xiao Chen; Wan-Cai Liu; Feng Zhu; Xiang-Wen Wu; Feng Xia; Miao-Chang Xie; Xia-Nian Cheng; Ka-Sing Lim; et al. (Journal of Pest Science, 2019)

Isolation and characterization of duck adenovirus 3 circulating in China - Shaohua Shi; Rongchang Liu; Chunhe Wan; Longfei Cheng; Zhen Chen; Guanghua Fu; Hongmei Chen; Qiuling Fu; Yu Huang (Archives of Virology, 2019)

2018 Continues Record Global Ocean Warming - Lijing Cheng; Jiang Zhu; John Abraham; Kevin E. Trenberth; John T. Fasullo; Bin Zhang; Fujiang Yu; Liying Wan; Xingrong Chen; Xiangzhou Song (Advances in Atmospheric Sciences, 2019)

Insights into removal of tetracycline by persulfate activation with peanut shell biochar coupled with amorphous Cu-doped FeOOH composite in aqueous solution - Jian Xu; Xueliang Zhang; Cheng Sun; Jinzhong Wan; Huan He; Fei Wang; Yuxuan Dai; Shaogui Yang; Yusuo Lin; Xinhua Zhan (Environmental Science and Pollution Research, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

RNA-Seq-mediated transcriptomic analysis of heat stress response in a polar Chlorella sp. (Trebouxiophyceae, Chlorophyta) - Sze-Wan Poong; Kok-Keong Lee; Phaik-Eem Lim; Tun-Wen Pai; Chiew-Yen Wong; Siew-Moi Phang; Chien-Ming Chen; Cing-Han Yang; Chun-Cheng Liu (Journal of Applied Phycology, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Collapse behavior and microstructural evolution of loess soils from the Loess Plateau of China - Wan-li Xie; Ping Li; Mao-sheng Zhang; Tian-e Cheng; Yong Wang (Journal of Mountain Science, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Effects of High Temperature on the Mechanical Properties of Chinese Marble - Zhen-nan Zhu; Hong Tian; Guo-sheng Jiang; Wan Cheng (Rock Mechanics and Rock Engineering, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Developmental transcriptome analysis of floral transition in Rosa odorata var. gigantea - Xuelian Guo; Chao Yu; Le Luo; Huihua Wan; Ni Zhen; Yushu Li; Tangren Cheng; Jia Wang; Huitang Pan; Qixiang Zhang (Plant Molecular Biology, 2018)

OPEN GLUME1: a key enzyme reducing the precursor of JA, participates in carbohydrate transport of lodicules during anthesis in rice - Xiaohui Li; Yihua Wang; Erchao Duan; Qi Qi; Kunneng Zhou; Qiuyun Lin; Di Wang; Yunlong Wang; Wuhua Long; Zhigang Zhao; Zhijun Cheng; Cailin Lei; et al. (Plant Cell Reports, 2018)

Resveratrol induces apoptosis and inhibits adipogenesis by stimulating the SIRT1-AMPKα-FOXO1 signalling pathway in bovine intramuscular adipocytes - Xiaomu Liu; Hongbo Zhao; Qing Jin; Wei You; Haijian Cheng; Yifan Liu; Enliang Song; Guifen Liu; Xiuwen Tan; Xianglun Zhang; Fachun Wan (Molecular and Cellular Biochemistry, 2018)

Transcriptome sequencing of an Antarctic microalga, Chlorella sp. (Trebouxiophyceae, Chlorophyta) subjected to short-term ultraviolet radiation stress - Sze-Wan Poong; Phaik-Eem Lim; Siew-Moi Phang; Chiew-Yen Wong; Tun-Wen Pai; Chien-Ming Chen; Cing-Han Yang; Chun-Cheng Liu (Journal of Applied Phycology, 2018)

Assessment of debris inputs from land into the river in the Three Gorges Reservoir Area, China - Jing Wan; Yonggui Wang; Meiling Cheng; Bernard A. Engel; Wanshun Zhang; Hong Peng (Environmental Science and Pollution Research, 2018)

The role of complementarity and selection effects in P acquisition of intercropping systems - Xiao-Fei Li; Cheng-Bao Wang; Wei-Ping Zhang; Le-Hua Wang; Xiu-Li Tian; Si-Cun Yang; Wan-Li Jiang; Jasper van Ruijven; Long Li (Plant and Soil, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Effects of the Oral Administration of K2Cr2O7 and Na2SeO3 on Ca, Mg, Mn, Fe, Cu, and Zn Contents in the Heart, Liver, Spleen, and Kidney of Chickens - Peng Chen; Yiran Zhu; Huiyu Wan; Yang Wang; Pan Hao; Ziqiang Cheng; Yongxia Liu; Jianzhu Liu (Biological Trace Element Research, 2017)

Reservoir quality and diagenesis of the Permian Lucaogou Formation tight carbonates in Jimsar Sag, Junggar Basin, West China - Yongqiang Yang; Longwei Qiu; Yingchang Cao; Cheng Chen; Dewen Lei; Ming Wan (Journal of Earth Science, 2017)

Semi-analytical and semi-numerical method for plane strain consolidation of double-layer foundation considering stress paths - Tao Cheng; Ke-Qin Yan; Jun-Jie Zheng; Xian-Feng Luo; Ding-Bang Zhang; Wan-Hui Xu; Ren-Jie Hu (European Journal of Environmental and Civil Engineering, 2017)

Risk alleles for IgA nephropathy-associated SNPs conferred completely opposite effects to idiopathic membranous nephropathy in Chinese Han - Xiaosong Qin; Chen Wang; Guanting Lu; Mengle Peng; Guixue Cheng; Hongquan Zhu; Yun Cao; Jianhua Liu; Yuzhong Li; Hong Cai; Funing Yang; Yanhong Liu; et al. (Immunologic Research, 2017)

A putative plastidial adenine nucleotide transporter, BRITTLE1-3, plays an essential role in regulating chloroplast development in rice (Oryza sativa L.) - Jia Lyu; Yihua Wang; Linglong Liu; Chunming Wang; Yulong Ren; Cheng Peng; Feng Liu; Yunlong Wang; Mei Niu; Di Wang; Ming Zheng; Kunneng Zhou; et al. (Journal of Plant Biology, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Co-occurrence and interactions of pollutants, and their impacts on soil remediation—A review - Shujing Ye; Guangming Zeng; Haipeng Wu; Chang Zhang; Jie Liang; Juan Dai; Zhifeng Liu; Weiping Xiong; Jia Wan; Piao Xu; Min Cheng (Critical Reviews in Environmental Science and Technology, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Selenium Administration Alleviates Toxicity of Chromium(VI) in the Chicken Brain - Pan Hao; Yiran Zhu; Shenghua Wang; Huiyu Wan; Peng Chen; Yang Wang; Ziqiang Cheng; Yongxia Liu; Jianzhu Liu (Biological Trace Element Research, 2017)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Difference of performance in response to disease admissions between daily time air quality indices and those derived from average and entropy functions - Li-Wei Lai; Wan-Li Cheng (Environmental Science and Pollution Research, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Effects of calcium at toxic concentrations of cadmium in plants - Danlian Huang; Xiaomin Gong; Yunguo Liu; Guangming Zeng; Cui Lai; Hassan Bashir; Lu Zhou; Dafei Wang; Piao Xu; Min Cheng; Jia Wan (Planta, 2017)

Life history and life table of the host-feeding parasitoid Hemiptarsenus varicornis (Hymenoptera: Eulophidae) - Xiao-Qin Cheng; Feng-Qin Cao; Yi-Bo Zhang; Jian-Yang Guo; Fang-Hao Wan; Wan-Xue Liu (Applied Entomology and Zoology, 2017)

A novel set of single-copy nuclear gene markers in white oak and implications for species delimitation - Jun Chen; Yan-Fei Zeng; Wan-Jin Liao; Peng-Cheng Yan; Jian-Guo Zhang (Tree Genetics & Genomes, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Antipsychotic use is a risk factor for hyponatremia in patients with schizophrenia: a 15-year follow-up study - Hang-Ju Yang; Wan-Ju Cheng (Psychopharmacology, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Ommaya reservoir in the treatment of cryptococcal meningitis - Baozhu Wei; Cheng Qian; Yang Liu; Xuan Lin; Jing Wan; Yanggan Wang (Acta Neurologica Belgica, 2017)

Young Seedling Stripe1 encodes a chloroplast nucleoid-associated protein required for chloroplast development in rice seedlings - Kunneng Zhou; Yulong Ren; Feng Zhou; Ying Wang; Long Zhang; Jia Lyu; Yihua Wang; Shaolu Zhao; Weiwei Ma; Huan Zhang; Liwei Wang; Chunming Wang; et al. (Planta, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Effects of anthropogenic activities on the heavy metal levels in the clams and sediments in a tropical river - Koe Wei Wong; Chee Kong Yap; Rosimah Nulit; Mohd Suhaimi Hamzah; Soo Kien Chen; Wan Hee Cheng; Ali Karami; Salman Abdo Al-Shami (Environmental Science and Pollution Research, 2017)

Microglia Activation and Polarization After Intracerebral Hemorrhage in Mice: the Role of Protease-Activated Receptor-1 - Shu Wan; Yingying Cheng; Hang Jin; Dewei Guo; Ya Hua; Richard F. Keep; Guohua Xi (Translational Stroke Research, 2016)

The induction of apoptosis in SGC-7901 cells through the ROS-mediated mitochondrial dysfunction pathway by a Ir(III) complex - Cheng Zhang; Shang-Hai Lai; Chuan-Chuan Zeng; Bing Tang; Dan Wan; De-Gang Xing; Yun-Jun Liu (JBIC Journal of Biological Inorganic Chemistry, 2016)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Differential allocation of carbon in fenced and clipped grasslands: a 13C tracer study in the semiarid Chinese Loess Plateau - Jie Wei; Weiguo Liu; Hao Wan; Jimin Cheng; Weijun Li (Plant and Soil, 2016)

A CONSTANS-like transcriptional activator, OsCOL13, functions as a negative regulator of flowering downstream of OsphyB and upstream of Ehd1 in rice - Peike Sheng; Fuqing Wu; Junjie Tan; Huan Zhang; Weiwei Ma; Liping Chen; Jiachang Wang; Jie Wang; Shanshan Zhu; Xiuping Guo; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Depot-specific effects of treadmill running and rutin on white adipose tissue function in diet-induced obese mice - Neng Chen; Ting Lei; Lili Xin; Lingmei Zhou; Jinbo Cheng; Liqiang Qin; Shufen Han; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2016)

Comparative Analysis of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) of Streptococcus thermophilus St-I and its Bacteriophage-Insensitive Mutants (BIM) Derivatives - Wan Li; Xin Bian; Smith Etareri Evivie; Gui-cheng Huo (Current Microbiology, 2016)

Wax crystal-sparse leaf 3 encoding a β-ketoacyl-CoA reductase is involved in cuticular wax biosynthesis in rice - Lu Gan; Xiaole Wang; Zhijun Cheng; Linglong Liu; Jiulin Wang; Zhe Zhang; Yulong Ren; Cailin Lei; Zhichao Zhao; Shanshan Zhu; Qibing Lin; Fuqing Wu; et al. (Plant Cell Reports, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells - Lachlan R. Gray; Hung On; Emma Roberts; Hao K. Lu; Michael A. Moso; Jacqueline A. Raison; Catherine Papaioannou; Wan-Jung Cheng; Anne M. Ellett; Jonathan C. Jacobson; Damian F. J. Purcell; Steve L. Wesselingh; et al. (Journal of NeuroVirology, 2016)

Composition, distribution and habitat effects of vascular plants on the vertical surfaces of an ancient city wall - Yanning Qiu; Bin J. W. Chen; Yanjuan Song; Zheng Y. X. Huang; Li Wan; Cheng Huang; Maosong Liu; Chi Xu (Urban Ecosystems, 2016)

BRITTLE SHEATH1 encoding OsCYP96B4 is involved in secondary cell wall formation in rice - Xiaole Wang; Zhijun Cheng; Zhichao Zhao; Lu Gan; Ruizhen Qin; Kunneng Zhou; Weiwei Ma; Baocai Zhang; Jiulin Wang; Huqu Zhai; Jianmin Wan (Plant Cell Reports, 2016)

Spatial and temporal characteristics of rainfall across Ganjiang River Basin in China - Yang Xiao; Xiang Zhang; Hui Wan; Yeqiao Wang; Cheng Liu; Jun Xia (Meteorology and Atmospheric Physics, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Extracting urban areas in China using DMSP/OLS nighttime light data integrated with biophysical composition information - Yang Cheng; Limin Zhao; Wei Wan; Lingling Li; Tao Yu; Xingfa Gu (Journal of Geographical Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Comparative analysis of transcriptional profiles of retinoic-acid-induced gene I-like receptors and interferons in seven tissues from ducks infected with avian Tembusu virus - Guanghua Fu; Cuiteng Chen; Yu Huang; Longfei Cheng; Qiuling Fu; Chunhe Wan; Shaohua Shi; Hongmei Chen; Wei Liu (Archives of Virology, 2016)

Effects of treadmill running and rutin on lipolytic signaling pathways and TRPV4 protein expression in the adipose tissue of diet-induced obese mice - Neng Chen; Jinbo Cheng; Lingmei Zhou; Ting Lei; Lihua Chen; Qiang Shen; Liqiang Qin; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2015)

Effects of TGF-β1 on the Proliferation and Apoptosis of Human Cervical Cancer Hela Cells In Vitro - Ming-Zhu Tao; Xia Gao; Tie-Jun Zhou; Qing-Xi Guo; Qiang Zhang; Cheng-Wan Yang (Cell Biochemistry and Biophysics, 2015)

Research on Acute Toxicity and Pharmacodynamics of Jinyulian Oral Solution - Wan-Qing Cheng; Zhen-Jian Zhang; Chuan-Bin Cao; Xiao-Wen Ye; Wang-Ping Pan; Si-Ying Ye; Bo Zhu (Cell Biochemistry and Biophysics, 2015)
A research on Jinyulian Oral Solution was conducted and the objectives were to discover its possible acute toxicity and antibacterial effects when used in vitro and in vivo. Regarding the acute toxicity test, Kunming mice were fed a maximum amount of the solution as their stomachs could hold, i.e., 40 mL kg −1 . To ascertain the minimum inhibitory concentration (MIC) of the solution, two types of germs, i.e., Staphylococcus aureus and Escherichia coli , were selected and tube dilution method was adopted. An antibacterial experimental model relying on animals’ body was developed for the researchers to observe the solution’s antibacterial effects. Test results showed that no abnormalities were discovered within 14 days after the initial date of testing and the mice grew as normal when fed with an amount of the solution 250 times of a normal clinical doze (In this case a man was assumed to weigh 60 kg.) and that the solution demonstrated obvious antibacterial effects on the two types of selected germs. The respective measured MIC 50 and MIC 90 values of the two germs were 3.2, 12.8, 6.4, and 25.6 mg L −1 . Therefore, it is reasonable to conclude that Jinyulian Oral Solution possesses no acute toxicity but obvious antibacterial effects on the two before-mentioned germs.

The Sensitivity of the Loa/Unload Response Ratio and Critical Region Selection Before Large Earthquakes - Huai-zhong Yu; Faren Zhou; Jia Cheng; Yong-ge Wan; Yong-xian Zhang (Pure and Applied Geophysics, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Experimental Investigation About Influence of Pre-existing Fracture on Hydraulic Fracture Propagation Under Tri-axial Stresses - Wan Cheng; Yan Jin; Qing Lin; Mian Chen; Yakun Zhang; Ce Diao; Bing Hou (Geotechnical and Geological Engineering, 2015)

Arbuscular mycorrhizal fungal community response to warming and nitrogen addition in a semiarid steppe ecosystem - Yong-Chan Kim; Cheng Gao; Yong Zheng; Xin-Hua He; Wei Yang; Liang Chen; Shi-Qiang Wan; Liang-Dong Guo (Mycorrhiza, 2015)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Loss of Function of the Cytochrome P450 Gene CYP78B5 Causes Giant Embryos in Rice - Yilin Chen; Linglong Liu; Yingyue Shen; Shijia Liu; Jiexue Huang; Qizhang Long; Wei Wu; Chunyan Yang; Hong Chen; Xiuping Guo; Zhijun Cheng; Ling Jiang; et al. (Plant Molecular Biology Reporter, 2015)

Horizontal arrangement of anodes of microbial fuel cells enhances remediation of petroleum hydrocarbon-contaminated soil - Yueyong Zhang; Xin Wang; Xiaojing Li; Lijuan Cheng; Lili Wan; Qixing Zhou (Environmental Science and Pollution Research, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Effects of Five Naturally Occurring Sugars on the Longevity, Oogenesis, and Nutrient Accumulation Pattern in Adult Females of the Synovigenic Parasitoid Neochrysocharis formosa (Hymenoptera: Eulophidae) - W Wang; S-L Lu; W-X Liu; L-S Cheng; Y-B Zhang; F-H Wan (Neotropical Entomology, 2014)

Activation of extrasynaptic GABAA receptors inhibits cyclothiazide-induced epileptiform activity in hippocampal CA1 neurons - Li Wan; Xu Liu; Zheng Wu; Wanting Ren; Shuzhen Kong; Raya Abou Dargham; Longzhen Cheng; Yun Wang (Neuroscience Bulletin, 2014)

Albino midrib 1, encoding a putative potassium efflux antiporter, affects chloroplast development and drought tolerance in rice - Peike Sheng; Junjie Tan; Mingna Jin; Fuqing Wu; Kunneng Zhou; Weiwei Ma; Yueqin Heng; Jiulin Wang; Xiuping Guo; Xin Zhang; Zhijun Cheng; Linglong Liu; et al. (Plant Cell Reports, 2014)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Contrasting patterns of ovarian development and oogenesis in two sympatric host-feeding parasitoids, Diglyphus isaea and Neochrysocharis formosa (Hymenoptera: Eulophidae) - Wan-Xue Liu; Wei Wang; Li-Sheng Cheng; Jian-Yang Guo; Fang-Hao Wan (Applied Entomology and Zoology, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

A Schiff-Based Colorimetric Fluorescent Sensor with the Potential for Detection of Fluoride Ions - Cheng-Yin Huang; Chin-Feng Wan; Jiun-Ly Chir; An-Tai Wu (Journal of Fluorescence, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Green-revertible Chlorina 1 (grc1) is required for the biosynthesis of chlorophyll and the early development of chloroplasts in rice - Jieqin Li; Yihua Wang; Juntao Chai; Lihua Wang; Chunming Wang; Wuhua Long; Di Wang; Yunlong Wang; Ming Zheng; Cheng Peng; Mei Niu; Jianmin Wan (Journal of Plant Biology, 2013)

Endoplasmic reticulum stress leads to lipid accumulation through upregulation of SREBP-1c in normal hepatic and hepatoma cells - Dian-liang Fang; Ying Wan; Wei Shen; Jie Cao; Zhong-xin Sun; Hui-hong Yu; Qin Zhang; Wen-hui Cheng; Juan Chen; Bo Ning (Molecular and Cellular Biochemistry, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Immunogenicity of a lettuce-derived vaccine candidate expressing the E2 protein against classical swine fever virus - Jinn-Chin Yiu; Cheng-Wei Liu; Ruei-Yuan Su; Wan-Jun Lai; Menq-Jiau Tseng; Sheng-Jung Ou (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Marker-assisted selection of Verticillium wilt resistance in progeny populations of upland cotton derived from mass selection-mass crossing - Cheng-Qi Li; Guan-Shen Liu; Hai-Hong Zhao; Li-Juan Wang; Xiao-Fei Zhang; Ying Liu; Wan-Yang Zhou; Liu-Liu Yang; Peng-Bo Li; Qing-Lian Wang (Euphytica, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Differential autophagic cell death under stress with ectopic cytoplasmic and mitochondrial-specific PPP2R2B in human neuroblastoma cells - Kang Fang; Hui-Fang Li; Chang-Heng Hsieh; Dan-Yu Li; Ding-Chieh Song; Wan-Ting Cheng; Zhi-Xuan Guo (Apoptosis, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Identification and assessment of heavy rainfall–induced disaster potentials in Taipei City - Jui-Sheng Chou; Kuo-Hsin Yang; Min-Yuan Cheng; Wan-Ting Tu (Natural Hazards, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

BEAK LIKE SPIKELET1 is Required for Lateral Development of Lemma and Palea in Rice - Xiaoding Ma; Zhijun Cheng; Fuqing Wu; Mingna Jin; Liguo Zhang; Feng Zhou; Jiulin Wang; Kunneng Zhou; Jian Ma; Qibing Lin; Cailin Lei; Jianmin Wan (Plant Molecular Biology Reporter, 2013)

Young Leaf Chlorosis 1, a chloroplast-localized gene required for chlorophyll and lutein accumulation during early leaf development in rice - Kunneng Zhou; Yulong Ren; Jia Lv; Yihua Wang; Feng Liu; Feng Zhou; Shaolu Zhao; Saihua Chen; Cheng Peng; Xin Zhang; Xiuping Guo; Zhijun Cheng; et al. (Planta, 2013)

Use of a bovine genome chip to identify new biological pathways for beef quality in cattle - Liu Guifen; Liu Xiaomu; Wan Fachun; Tan Xiuwen; Cheng Haijian; Song Enliang (Molecular Biology Reports, 2012)

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Glycosylation potential of human prostate cancer cell lines - Yin Gao; Vishwanath B. Chachadi; Pi-Wan Cheng; Inka Brockhausen (Glycoconjugate Journal, 2012)

An analytical investigation of a sequence of unusual springtime ozone episodes over metropolitan Taichung in 2007 - Wan-Li Cheng; Li-Wei Lai; Walter Den; Shu-Ying Wang; Pay-Liam Lin; Chueh-Ying Pai (Meteorology and Atmospheric Physics, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

Organ Histopathological Changes and its Function Damage in Mice Following Long-term Exposure to Lanthanides Chloride - Jie Cheng; Na Li; Jingwei Cai; Zhe Cheng; Renping Hu; Qian Zhang; Fangfang Wan; Qingqing Sun; Suxing Gui; Xuezi Sang; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China - Yan Qin; YanHe Li; Feng Liu; KeJun Hou; DeFang Wan; Cheng Zhang (Science China Earth Sciences, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Successful vitrification of mouse ovaries using less-concentrated cryoprotectants with Supercool X-1000 supplementation - Xiuwen Tan; Enliang Song; Xiaomu Liu; Guifen Liu; Haijian Cheng; Fachun Wan (In Vitro Cellular & Developmental Biology - Animal, 2012)

Wax crystal-sparse leaf2, a rice homologue of WAX2/GL1, is involved in synthesis of leaf cuticular wax - Bigang Mao; Zhijun Cheng; Cailin Lei; Fenghua Xu; Suwei Gao; Yulong Ren; Jiulin Wang; Xin Zhang; Jie Wang; Fuqing Wu; Xiuping Guo; Xiaolu Liu; et al. (Planta, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

PCBP2 siRNA Reverses the Alcohol-induced Pro-fibrogenic Effects in Hepatic Stellate Cells - Ravi S. Shukla; Bin Qin; Yu-Jui Yvonne Wan; Kun Cheng (Pharmaceutical Research, 2011)

A Random Comparative Study of Terbinafine Versus Griseofulvin in Patients with Tinea Capitis in Western China - S. Deng; H. Hu; P. Abliz; Z. Wan; A. Wang; W. Cheng; R. Li (Mycopathologia, 2011)

Molecular cloning of allelopathy related genes and their relation to HHO in Eupatorium adenophorum - Huiming Guo; Xixiang Pei; Fanghao Wan; Hongmei Cheng (Molecular Biology Reports, 2011)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Trend of Santonian (Late Cretaceous) atmospheric CO2 and global mean land surface temperature: Evidence from plant fossils - ChuanBiao Wan; DeHai Wang; ZhanPing Zhu; Cheng Quan (Science China Earth Sciences, 2011)

Plasminogen K5 activates mitochondrial apoptosis pathway in endothelial cells by regulating Bak and Bcl-xL subcellular distribution - Xiaoqiong Gu; Yachao Yao; Rui Cheng; Yang Zhang; Zhiyu Dai; Genping Wan; Zhonghan Yang; Weibin Cai; Guoquan Gao; Xia Yang (Apoptosis, 2011)

Critical sensitivity of load/unload response ratio and stress accumulation before large earthquakes: example of the 2008 Mw7.9 Wenchuan earthquake - Huai-zhong Yu; Jia Cheng; Qing-yong Zhu; Yong-ge Wan (Natural Hazards, 2011)

Preliminary Study of Metal in Yak (Bos grunniens) Milk from Qilian of the Qinghai Plateau - Wan-cheng Sun; Yi-hao Luo; Hai-qing Ma (Bulletin of Environmental Contamination and Toxicology, 2011)

Fine mapping of qSTV11 KAS , a major QTL for rice stripe disease resistance - Ying-Xin Zhang; Qi Wang; Ling Jiang; Ling-Long Liu; Bao-Xiang Wang; Ying-Yue Shen; Xia-Nian Cheng; Jian-min Wan (Theoretical and Applied Genetics, 2011)

Isolation and characterization of Vibrio metschnikovii causing infection in farmed Portunus trituberculatus in China - Xihe Wan; Hui Shen; Libao Wang; Yongxu Cheng (Aquaculture International, 2011)

Overexpression of SlCZFP1, a Novel TFIIIA-type Zinc Finger Protein from Tomato, Confers Enhanced Cold Tolerance in Transgenic Arabidopsis and Rice - Xin Zhang; Xiuping Guo; Cailin Lei; Zhijun Cheng; Qibin Lin; Jiulin Wang; Fuqing Wu; Jie Wang; Jianmin Wan (Plant Molecular Biology Reporter, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

A rice β-1,3-glucanase gene Osg1 is required for callose degradation in pollen development - Linglin Wan; Wenjun Zha; Xiaoyan Cheng; Chuan Liu; Lu Lv; Caixiang Liu; Zhanqi Wang; Bo Du; Rongzhi Chen; Lili Zhu; Guangcun He (Planta, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Agrobacterium-mediated transformation of Eupatorium adenophorum - Huiming Guo; Yongqiang Zhang; Fanghao Wan; Hongmei Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Seismic monitoring of western Pacific typhoons - Wu-Cheng Chi; Wan-Jou Chen; Ban-Yuan Kuo; David Dolenc (Marine Geophysical Research, 2010)

Differential Cardiopulmonary Effects of Size-Fractionated Ambient Particulate Matter in Mice - Haiyan Tong; Wan-Yun Cheng; James M. Samet; M. Ian Gilmour; Robert B. Devlin (Cardiovascular Toxicology, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

The vacuolar ATPase in bone cells: a potential therapeutic target in osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Cheng-Wan Li; Jian-Ping Li; Yu Wang (Molecular Biology Reports, 2010)

Transcriptomics Analysis Identified Candidate Genes Colocalized with Seed Dormancy QTLs in Rice (Oryza sativa L.) - Huaide Qin; Fuqing Wu; Kun Xie; Zhijun Cheng; Xiuping Guo; Xin Zhang; Jie Wang; Cailin Lei; Jiulin Wang; Long Mao; Ling Jiang; Jianmin Wan (Journal of Plant Biology, 2010)

cDNA Cloning, Prokaryotic Expression, Polyclonal Antibody Preparation of the Auxin-Binding Protein 1 Gene from Grape Berry - Si-Bao Wan; Wei Wang; Mei Luo; Wei-Dong Huang; Jing-Yuan Yin; Ji-Cheng Zhan (Plant Molecular Biology Reporter, 2010)

Spatial variation law of vertical derivative zero points for potential field data - Wan-Yin Wang; Gong-Cheng Zhang; Jian-She Liang (Applied Geophysics, 2010)

Seasonal variations in planktonic foraminiferal flux and the chemical properties of their shells in the southern South China Sea - Sui Wan; ZhiMin Jian; XinRong Cheng; PeiJun Qiao; RuJian Wang (Science China Earth Sciences, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

A novel normonoterpenoid from the stems of Cinnamomum reticulatum Hay - Ming-Jen Cheng; Wen-Li Lo; Wan-Shan Tseng; Hung-Chun Yeh; Chung-Yi Chen (Natural Product Research, 2010)

Air temperature change due to human activities in Taiwan for the past century - Li‐Wei Lai; Wan‐Li Cheng (International Journal of Climatology, 2010)
The purpose of this study was to statistically examine air temperature change and to analyse the anthropogenic factors potentially influencing air temperature changes in Taiwan for the period 1897–2005 using homogenized temperature measurement time series. In this study, the standard normal homogeneity test was used to attain homogeneity of all air temperature series. To analyse air temperature data from 1897 to 2005, a time‐series regression model and a product–moment correlation were used. The annual mean maximum temperatures ( T max ), annual mean minimum temperatures ( T min ) and the number of days in which the air temperature ≥ 30 °C increased significantly in most regions in Taiwan, and the rate of increase for T min was higher than that of T max . In other words, in the past century the night temperatures have become higher and the period of hot days in Taiwan have become longer. However, over the past century and before 1962, the trend of T max in central Taiwan (i.e. Jihyuehtan and Taichung) decreased significantly, which is inconsistent with greenhouse gas warming and general warming observed in other sites in Taiwan. Furthermore, during the economic growth experienced between 1962 and 2005, the rates of increase for T max and T min in major cities with similar climate conditions (i.e. Tainan and Kaohsiung) were significantly different, as were the correlation coefficients between temperature changes and the number of various economic sectors in the cities. The results of these statistical analyses suggest that human activities strongly affected air temperature changes in these urban areas. The obvious lack of spatial homogeneity indicates that various non‐greenhouse gas processes have played roles in climate change in Taiwan, and these factors must be considered when analysing long‐term air temperature variations. Caution should be exercised when using grid data to assess temperature trends at the grid‐box level. Copyright © 2009 Royal Meteorological Society

Development and identification of a wheat-Psathyrostachys huashanica addition line carrying HMW-GS, LMW-GS and gliadin genes - Ji-Xin Zhao; Wan-Quan Ji; Jun Wu; Xin-Hong Chen; Xue-Ni Cheng; Jian-Wei Wang; Yu-Hui Pang; Shu-Hui Liu; Qun-Hui Yang (Genetic Resources and Crop Evolution, 2010)

Antagonism between abscisic acid and ethylene in Arabidopsis acts in parallel with the reciprocal regulation of their metabolism and signaling pathways - Wan-Hsing Cheng; Ming-Hau Chiang; San-Gwang Hwang; Pei-Chi Lin (Plant Molecular Biology, 2009)

Elevated expression of L-selectin ligand in lymph node-derived human prostate cancer cells correlates with increased tumorigenicity - Prakash Radhakrishnan; Ming-Fong Lin; Pi-Wan Cheng (Glycoconjugate Journal, 2009)

Genetic analysis of a novel dominant rice dwarf mutant 986083D - Ruizhen Qin; Yang Qiu; Zhijun Cheng; Xueyan Shan; Xiuping Guo; Huqu Zhai; Jianmin Wan (Euphytica, 2008)

Transcriptional analysis of a major capsid protein gene from Spodoptera exigua ascovirus 5a - T. Z. Salem; C. M. Turney; L. Wang; J. Xue; X.-F. Wan; X.-W. Cheng (Archives of Virology, 2008)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Modified Grey Model for Estimating Traffic Tunnel Air Quality - Cheng-Chung Lee; Terng-Jou Wan; Chao-Yin Kuo; Chung-Yi Chung (Environmental Monitoring and Assessment, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Capillary gas chromatographic determination of dimethachlon residues in fresh tobacco leaves and cut-tobacco - Hong-cheng Liu; Qi-wan Li; Li-bin Tang (Journal of Zhejiang University-SCIENCE B, 2007)

QTL analysis for rice grain length and fine mapping of an identified QTL with stable and major effects - X. Y. Wan; J. M. Wan; L. Jiang; J. K. Wang; H. Q. Zhai; J. F. Weng; H. L. Wang; C. L. Lei; J. L. Wang; X. Zhang; Z. J. Cheng; X. P. Guo (Theoretical and Applied Genetics, 2006)

Estimating Air Quality in a Traffic Tunnel Using a Forecasting Combination Model - Cheng-Chung Lee; Terng-Jou Wan; Chao-Yin Kuo; Chung-Yi Chung (Environmental Monitoring and Assessment, 2006)

Using the Flow Cytometry to Quantify the Giardia Cysts and Cryptosporidium Oocysts in Water Samples - Bing-Mu Hsu; Nan-Min Wu; Hung-Der Jang; Feng-Cheng Shih; Min-Tao Wan; Chien-Min Kung (Environmental Monitoring and Assessment, 2005)

Activation of CMV promoter-controlled glycosyltransferase and β -galactosidase glycogenes by butyrate, tricostatin A, and 5-Aza-2′-deoxycytidine - Kyung Hyun Choi; Hesham Basma; Jaswant Singh; Pi-Wan Cheng (Glycoconjugate Journal, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Odorous swine wastewater treatment by purple non-sulfur bacteria, Rhodopseudomonas palustris, isolated from eutrophicated ponds - Myung Kyum Kim; Kyung-Min Choi; Cheng-Ri Yin; Ki-Young Lee; Wan-Taek Im; Ju Hyoung Lim; Sung-Taik Lee (Biotechnology Letters, 2004)

One-Tube Nested RT-PCR Enabled by Using a Plastic Film and its Application for the Rapid Detection of SARS-Virus - Sheng-Ce Tao; Di Jiang; Hong-Li Lu; Wan-Li Xing; Yu-Xiang Zhou; Jing Cheng (Biotechnology Letters, 2004)

Isolation and Characterization of Bacteria Capable of Degrading Phenol and Reducing Nitrate Under Low-Oxygen Conditions - Seung-Hun Baek; Kyoung-Ho Kim; Cheng-Ri Yin; Che Ok Jeon; Wan-Taek Im; Kwang-Kyu Kim; Sung-Taik Lee (Current Microbiology, 2003)

Downregulation of PTEN/MMAC/TEP1 expression in human prostate cancer cell line DU145 by growth stimuli - Dhundy R. Bastola; Gurcharan S. Pahwa; Ming-Fong Lin; Pi-Wan Cheng (Molecular and Cellular Biochemistry, 2002)

Regional turbulent statistics over contrasting natural surfaces - T. J. Lyons; Li Fuqin; J. M. Hacker; Wan-Li Cheng; Huang Xinmei (Meteorology and Atmospheric Physics, 2001)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Spatio-Temporal Variations of Sulphur Dioxide Patterns with Wind Conditions in Central Taiwan - Wan-Li Cheng (Environmental Monitoring and Assessment, 2001)

A vertical profile of Ozone concentration in the atmosphericboundary layer over central Taiwan - Wan-Li Cheng (Meteorology and Atmospheric Physics, 2000)

Acute Toxicity of Inorganic Chloramines to Daphnia magna in Two Types of Dilution Water - M. T. Wan; R. G. Watts; W. Cheng (Bulletin of Environmental Contamination and Toxicology, 2000)

Acute Toxicity of Inorganic Chloramines to Daphnia magna in Two Types of Dilution Water - M. T. Wan; R. G. Watts; W. Cheng (Bulletin of Environmental Contamination and Toxicology, 2000)

Validation of the Acute Toxicity of Inorganic Chloramines to the Fresh Water Invertebrate Daphnia magna - M. T. Wan; G. Van Aggelen; W. Cheng; C. Buday (Bulletin of Environmental Contamination and Toxicology, 2000)

Acute Toxicity of Chlorine-Produced Oxidants (CPO) to the Marine Invertebrates Amphiporeia virginiana and Eohaustorius washingtonianus - M. T. Wan; G. Van Aggelen; W. Cheng; R. G. Watts (Bulletin of Environmental Contamination and Toxicology, 2000)

Development of monoclonal antibodies against bovine mucin core 2 β6 N-acetylglucosaminyltransferase - Cheng-Ming Li; Nirmal Joshee; Kenneth B. Adler; Pi-Wan Cheng (Glycoconjugate Journal, 1999)

Genetic evidence that invertase-mediated release of hexoses is critical for appropriate carbon partitioning and normal seed development in maize - Wan-Hsing Cheng; Prem S. Chourey (Theoretical and Applied Genetics, 1999)

Altered expression of sialylated carbohydrate antigens in HT29 colonic carcinoma cells - David R. Mack; Pi-Wan Cheng; Fulvio Perini; Shu Wei; Michael A. Hollingsworth (Glycoconjugate Journal, 1998)

Hydrogen peroxide-induced expression of the proto-oncogenes, c-jun, c-fos and c-myc in rabbit lens epithelial cells - David Wan-Cheng Li; Abraham Spector (Molecular and Cellular Biochemistry, 1997)